Multilayer film having at least three layers and method for producing same - Patents.com
By using improved polyethylene composition and thin film thickness in the core layer of the multilayer film, the problem of difficulty in improving endurance and reducing costs in the prior art is solved, and efficient film performance maintenance is achieved.
Patent Information
- Application Number
- JP2022503809
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-06
- Filing Date
- 2020-08-04
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2040-08-04
AI Technical Summary
Existing multilayer films are difficult to maintain sufficient endurance and reduce material costs while improving the balance between fouling and membrane coefficients, especially without using polyamide core layers.
A multilayer film structure is employed, wherein the core layer contains an improved polyethylene composition with a single peak elastic distribution over the temperature range and maintains endurance and creep resistance by thinning the overall film thickness.
The multilayer film is achieved while maintaining high endurance and creep resistance while reducing material costs and maintaining excellent performance while reducing film thickness.
Smart Images

Figure 0007649773000027 
Figure 0007649773000028 
Figure 0007649773000029
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Patent Application No. 62 / 883,469, filed August 6, 2019, and U.S. Provisional Patent Application No. 62 / 883,467, filed August 6, 2019, the disclosures of which are incorporated herein by reference in their entireties.
[0002] FIELD OF THE DISCLOSURE
[0002] Embodiments described herein relate generally to multilayer films, and specifically to multilayer films comprising polyethylene. [Background technology]
[0003] Improving sustainability is a goal for manufacturers of multilayer films, including polyethylene. It would therefore be beneficial for monolayer and multilayer polymeric films, which may include blown or cast films, to exhibit toughness while allowing for reduced material costs, for example, by downgauging (i.e., using thinner film thicknesses) or by reducing or eliminating relatively expensive materials such as polyamide. Summary of the Invention
[0004] In conventional multilayer films, the inclusion of a polyamide core layer in the multilayer film structure may offer a balance of desirable film properties between dart coefficient and film coefficient. However, the incorporation of a polyamide core layer may increase process complexity, increase the complexity of the film structure, produce a non-recyclable multilayer film, and increase material costs. However, typically, without the incorporation of a polyamide core layer, attempts to improve the coefficient through film modification may result in a loss of dart, and attempts to improve dart typically result in a loss of coefficient. Furthermore, it is often difficult to obtain a polymer film with sufficient toughness while allowing for a reduction in material costs through downgauging.
[0005] Thus, a need exists for multilayer films that exhibit physical properties such as dart / bag drop resistance, puncture resistance, tear resistance, and creep resistance that meet customer and industry requirements. In some embodiments, these multilayer films can maintain physical properties that meet customer and industry requirements even at reduced thicknesses or without a polyamide core layer.
[0006] The present disclosure, in various embodiments, meets those needs by providing a multilayer film including at least three layers that provide a balance of stiffness and abuse properties (e.g., dart, puncture energy, tear). Such multilayer films may include a polyethylene composition in a core layer that exhibits an improved balance of toughness and creep resistance. Furthermore, when reducing the overall thickness of a multilayer body including a polyethylene composition in a core layer, the multilayer film may still exhibit an improved balance of toughness and creep resistance compared to conventional multilayer films.
[0007] According to at least one embodiment, a multilayer film is provided. The multilayer film embodiment may include a first layer including a polyethylene composition, a second layer including a first polyolefin, and a third layer including a second polyolefin. The first layer may be disposed between the second layer and the third layer. The first polyolefin and the second polyolefin may be the same or different in composition. The polyethylene composition may comprise: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile measured by improved comonomer composition distribution (iCCD) analysis, wherein the first polyethylene fraction area is the area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; and (b) a second polyethylene fraction having a single peak in a temperature range of 95°C to 120°C in an elution profile measured by iCCD analysis, wherein the second polyethylene fraction area is the area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C, wherein the polyethylene composition has a molecular weight of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min, the first polyethylene fraction area comprising at least 40% of the total area of the dissolution profile, 2 Polyethylene fraction area To versus do No. 1 The ratio of the areas of the polyethylene fractions of the first and second polyethylene fractions is 0.75 to 2.5, and the width of the single peak of the second polyethylene fraction at 50 percent of the peak height is less than 5.0°C.
[0008] According to at least one further embodiment, a multilayer film is provided. The multilayer film embodiment includes a first layer, 0.910 to 0.936 g / cm 3 and a second layer comprising a first linear low density polyethylene having a density of 0.910 to 0.936 g / cm. 3The first linear low density polyethylene and the second linear low density polyethylene may have the same or different composition. The first layer may be disposed between the second layer and the third layer. The first layer may comprise 10% to 80% by weight of the total weight of the multilayer film. The first layer may comprise a polyethylene composition. The polyethylene composition may comprise: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile measured by improved comonomer composition distribution (iCCD) analysis, wherein the first polyethylene fraction area is the area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; and (b) a second polyethylene fraction having a single peak in a temperature range of 95°C to 120°C in an elution profile measured by iCCD analysis, wherein the second polyethylene fraction area is the area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C, the polyethylene composition having a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min, the first polyethylene fraction area comprising at least 40% of the total area of the dissolution profile, 2 Polyethylene fraction area To versus do No. 1 The ratio of the areas of the polyethylene fractions of the first and second polyethylene fractions is 0.75 to 2.5, and the width of the single peak of the second polyethylene fraction at 50 percent of the peak height is less than 5.0°C.
[0009] According to at least one further embodiment, a multilayer film is provided. The multilayer film embodiment may include a first layer, a second layer, and a third layer. The first layer may be disposed between the second layer and the third layer. The first layer may have a modulus of 0.940 g / cm as measured according to ASTM 742. 3 ~0.970g / cm 3The second layer may comprise a high density polyethylene composition having a density of 0.910 g / cm and a polyethylene composition. The second layer may comprise at least 50 wt. % of a first linear low density polyethylene based on the total weight of the second layer, the first linear low density polyethylene having a density of 0.910 g / cm. 3 ~0.936g / cm 3 The third layer may comprise at least 50 wt. % of a second linear low density polyethylene based on the total weight of the third layer, the second linear low density polyethylene having a density of 0.910 g / cm 3 ~0.936g / cm 3 The first linear low density polyethylene and the second linear low density polyethylene may have the same or different compositions. The polyethylene composition may comprise: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile measured by an improved comonomer composition distribution (iCCD) analysis method, the first polyethylene fraction area being the area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; and (b) a second polyethylene fraction having a single peak in a temperature range of 95°C to 120°C in an elution profile measured by an iCCD analysis method, the second polyethylene fraction area being the area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C, the polyethylene composition having a molecular weight of 0.924 g / cm. 3 ~0.936g / cm 3 and a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min, the first polyethylene fraction area comprising at least 40% of the total area of the dissolution profile, 2 Polyethylene fraction area To versus do No. 1 The ratio of the areas of the polyethylene fractions of the first and second polyethylene fractions is 0.75 to 2.5, and the width of the single peak of the second polyethylene fraction at 50 percent of the peak height is less than 5.0°C.
[0010] According to at least one further embodiment, a multilayer film is provided. The multilayer film embodiment can include a first layer, a second layer, and a third layer. The first layer can be disposed between the second layer and the third layer. The first layer can have a modulus of 0.940 g / cm 3 ~0.970g / cm 3 and a first polyethylene having a density of 0.924 g / cm 3 ~0.936g / cm 3 The second layer may comprise a first polyethylene composition having a density of 0.940 g / cm 3 ~0.970g / cm 3 A second polyethylene having a density of 0.916 g / cm 3 ~0.935g / cm 3 a first low density polyethylene composition having a density of 0.924 g / cm 3 ~0.936g / cm 3 The third layer may comprise a second polyethylene composition having a density of 0.916 g / cm 3 ~0.935g / cm 3 and a second low density polyethylene composition having a density of 0.924 g / cm 3 ~0.936g / cm 3and a third polyethylene composition having a density of 0.1 to 1.0. The first polyethylene and the second polyethylene may be of the same or different composition. The first low density polyethylene and the second low density polyethylene may be of the same or different composition. The first polyethylene composition, the second polyethylene composition, and the third polyethylene composition may be of the same or different compositions and each may comprise: (a) a first polyethylene fraction having a single peak in an elution profile measured by an improved comonomer composition distribution (iCCD) analysis method in a temperature range of 45°C to 87°C, wherein the first polyethylene fraction area is the area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; and (b) a second polyethylene fraction having a single peak in an elution profile measured by an iCCD analysis method in a temperature range of 95°C to 120°C, wherein the second polyethylene fraction area is the area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C, wherein the polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min, the first polyethylene fraction area comprising at least 40% of the total area of the dissolution profile, 2 Polyethylene fraction area To versus do No. 1 The ratio of the areas of the polyethylene fractions of the first and second polyethylene fractions is 0.75 to 2.5, and the width of the single peak of the second polyethylene fraction at 50 percent of the peak height is less than 5.0°C.
[0011] These and other embodiments are described in more detail in the following detailed description taken in conjunction with the accompanying drawings. [Brief description of the drawings]
[0012] The following detailed description of certain embodiments of the present disclosure can be best understood when read in conjunction with the following drawings, in which like structure is indicated with like reference numerals and in which:
[0013] [Figure 1] 1A-1C are schematic diagrams illustrating an iCCD elution profile according to one or more embodiments described herein. [Diagram 2] 1 graphically illustrates an iCCD elution profile for the polyethylene composition of Example 1, according to one or more embodiments described herein. [Diagram 3] 1 illustrates a schematic of a reactor system useful for producing polyethylene according to one or more embodiments described herein. [Figure 4] 1 illustrates a schematic of another reactor system useful for producing polyethylene according to one or more embodiments described herein. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] Certain embodiments of the present application will now be described. These embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the claimed subject matter to those skilled in the art.
[0015] Unless stated to the contrary, implied from the context, or customary in the art, all parts and percentages are by weight, all temperatures are in degrees Celsius, and all test methods are current as of the filing date of this disclosure.
[0016] The term "polymer" refers to a polymeric compound prepared by polymerizing monomers, whether of the same or different kinds. Thus, the generic term polymer generally encompasses the term "homopolymer," which refers to a polymer prepared from only one type of monomer, as well as "copolymer," which refers to a polymer prepared from two or more different types of monomers. As used herein, the term "interpolymer" refers to a polymer prepared by polymerization of at least two different types of monomers. Thus, the generic term interpolymer includes copolymers and polymers prepared from three or more different types of monomers, such as terpolymers.
[0017] "Polyethylene" or "ethylene-based polymer" shall mean a polymer containing more than 50 mol% units derived from ethylene monomers. This includes ethylene-based homopolymers or copolymers (meaning that the units are derived from two or more comonomers). Common forms of ethylene-based polymers known in the art include, but are not limited to, low density polyethylene (LDPE), linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), single-site catalyzed linear low density polyethylene (m-LLDPE), which includes both linear and substantially linear low density resins, medium density polyethylene (MDPE), and high density polyethylene (HDPE).
[0018] As used herein, the term "composition" refers to a mixture of materials that make up the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0019] As used herein, the term "polypropylene" or "propylene-based polymer" refers to a polymer composed of units derived from greater than 50 mole percent propylene monomers in polymerized form, including propylene homopolymer, random copolymer polypropylene, impact copolymer polypropylene, propylene / α-olefin copolymer, and propylene / α-olefin copolymer.
[0020] The term "LDPE", sometimes referred to as "high pressure ethylene polymer" or "highly branched polyethylene", is defined to mean that the polymer is partially or fully homopolymerized or copolymerized in an autoclave or tubular reactor at pressures in excess of 14,500 psi (100 MPa) by the use of free radical initiators such as peroxides (see, for example, U.S. Pat. No. 4,599,392, incorporated herein by reference). LDPE resins typically have a viscosity of 0.916 g / cm. 3 ~0.940g / cm 3 The density is in the range of
[0021] The term "LLDPE" includes resins made using Ziegler-Natta catalyst systems, as well as resins made using single-site catalysts, including but not limited to bismetallocene catalysts (sometimes referred to as "m-LLDPE"), phosphinimine, and constrained geometry catalysts, and postmetallocene molecular catalysts, including but not limited to bis(biphenylphenoxy) catalysts (also referred to as polyaryloxy ether catalysts). LLDPE includes linear, substantially linear, or heterogeneous ethylene-based copolymers or homopolymers. LLDPE contains less long chain branching than LDPE and includes substantially linear ethylene polymers as further defined in U.S. Patent Nos. 5,272,236, 5,278,272, 5,582,923, and 5,733,155, homogeneously branched linear ethylene polymer compositions such as those in U.S. Patent No. 3,645,992, heterogeneously branched ethylene polymers such as those prepared according to the process disclosed in U.S. Patent No. 4,076,698, and blends thereof (such as those disclosed in U.S. Patent Nos. 3,914,342 and 5,854,045). LLDPE resins may be made by gas phase, solution phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0022] The term "MDPE" means 0.924 g / cm 3 ~0.942g / cm 3 "MDPE" refers to polyethylene having a density of 100 to 2000 nm. "MDPE" is typically made using chromium or Ziegler-Natta catalysts, or using single-site catalysts, including but not limited to substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphinimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy).
[0023] The term "HDPE" refers to any polymer having a viscosity of about 0.935 g / cm, typically prepared using a single-site catalyst, including, but not limited to, Ziegler-Natta, chromium, or substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy). 3 Super ~ maximum approx. 0.980g / cm 3 It refers to polyethylene having a density of
[0024] The term "ULDPE" refers to any ULDPE having a viscosity of 0.855 g / cm or less that is generally prepared using a single-site catalyst, including, but not limited to, Ziegler-Natta, chromium, or substituted mono- or bis-cyclopentadienyl catalysts (typically referred to as metallocenes), constrained geometry catalysts, phosphimine catalysts, and polyaryloxy ether catalysts (typically referred to as bisphenylphenoxy). 3 ~0.912g / cm 3 ULDPE refers to polyethylene with a density of 0.855 g / cm. ULDPE includes, but is not limited to, polyethylene (ethylene-based) plastomers and polyethylene (ethylene-based) elastomers. Polyethylene (ethylene-based) elastomer plastomers generally have a density of 0.855 g / cm. 3 ~0.912g / cm 3 has a density of
[0025] "Blend", "polymer blend" and like terms refer to a composition of two or more polymers. Such blends may or may not be miscible. Such blends may or may not be phase separated. Such blends may or may not contain one or more domain configurations as determined from transmission electron spectroscopy, light scattering, X-ray scattering, and any other method known in the art. A blend is not a laminate, although one or more layers of a laminate may contain the blend. Such blends may be formed as dry blends, in situ (e.g., in a reactor), as melt blends, or using other techniques known to those skilled in the art.
[0026] "Multilayer structure" or "multilayer film" means any structure having two or more layers. For example, a multilayer structure (e.g., a film) may have two, three, four, five, or more layers. A multilayer structure may be described as having layers designated by letters. For example, a three-layer structure designated as A / B / C may have a core layer B and two outer layers A and C. Similarly, a structure having two core layers B and C and two outer layers A and D would be designated A / B / C / D.
[0027] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed. For the avoidance of any doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymeric or otherwise, unless otherwise stated to the contrary. In contrast, the term "consisting essentially of" excludes from the scope of any succeeding description any other components, steps, or procedures, except those that are not essential to operability. The term "consisting of" excludes any components, steps, or procedures not specifically defined or listed.
[0028] Multilayer Film Reference is now made to the multilayer film embodiments described herein. The multilayer film embodiments described herein can include at least three layers.
[0029] The multilayer film of the present disclosure may include at least three layers, and even as many as 13 or more layers. The number of layers of the multilayer film may depend on numerous factors, including, for example, the composition of each layer of the multilayer film, the desired properties of the multilayer film, the desired end use of the multilayer film, the manufacturing process of the multilayer film, and the like. The multilayer film may be a three-layer structure designated as A / B / C, where the first layer may be designated as A, the second layer may be designated as B, and the third layer may be designated as C. In some embodiments, the first layer may be referred to as a "core layer." In some embodiments, one or both of the second and third layers may be referred to as a "skin layer" or "outer layer." In embodiments, the first layer may be disposed between the second and third layers. In further embodiments, the second and third layers may be the outermost layers of the multilayer film. As used herein, the outermost layer of a multilayer film may be understood to mean that there may not be another layer deposited on the outermost layer such that the outermost layer is in direct contact with the surrounding air.
[0030] In embodiments, the first layer and the second layer, the first layer and the third layer, or both may be in direct contact with each other. As used herein, "direct contact" means that there may not be any other layer disposed between the two layers that are in direct contact with each other. In other embodiments, the multilayer film may include one or more additional layers, such as one or more tie layers, which may be disposed between the first layer (core layer) and the second layer (outer layer), between the first layer (core layer) and the third layer (another outer layer), or both.
[0031] As described in more detail later in this disclosure, the multilayer film may include a first layer comprising a polyethylene composition, a second layer comprising a first polyolefin, and a second layer comprising a second polyolefin. The first polyolefin and the second polyolefin may be the same or different in composition. It is understood that any of the aforementioned layers may further include one or more additives known to those skilled in the art, such as plasticizers, stabilizers including viscosity stabilizers, hydrolysis stabilizers, primary and secondary antioxidants, UV absorbers, antistatic agents, dyes, pigments, or other colorants, inorganic fillers, flame retardants, lubricants, reinforcing agents such as glass fibers and flakes, synthetic (e.g., aramid) fibers or pulps, foaming or blowing agents, processing aids, slip additives, antiblocking agents such as silica or talc, release agents, tackifying resins, or combinations of two or more thereof. Inorganic fillers such as calcium carbonate and the like and the like may also be incorporated into one or more of the first layer, the second layer, the third layer, and combinations thereof. In some embodiments, the first layer, second layer, third layer, and combinations may each include up to 5 weight percent of such additional additives, based on the total weight of the respective layer. All individual values and subranges from 0 wt% to 5 wt% are included and disclosed herein, for example, the total amount of additives in the first layer, second layer, or third layer may be 0.5 wt% to 5 wt%, 0.5 wt% to 4 wt%, 0.5 wt% to 3 wt%, 0.5 wt% to 2 wt%, 0.5 wt% to 1 wt%, 1 wt% to 5 wt%, 1 wt% to 4 wt%, 1 wt% to 3 wt%, 1 wt% to 2 wt%, 2 wt% to 5 wt%, 2 wt% to 4 wt%, 2 wt% to 3 wt%, 3 wt% to 5 wt%, 3 wt% to 4 wt%, or 4 wt% to 5 wt%, based on the total weight of the respective layer. The incorporation of the additives can be carried out by any known process such as, for example, dry blending, extrusion of a mixture of the various components, conventional masterbatch techniques, etc.
[0032] The multilayer film of the present invention can have a variety of thicknesses. The thickness of the multilayer film can depend on a number of factors, including, for example, the number of layers of the multilayer film, the composition of the layers of the multilayer film, the desired properties of the multilayer film, the desired end use of the film, the manufacturing process of the multilayer film, etc. In an embodiment, the multilayer film can have a thickness of less than 500 micrometers (μm or microns). In other embodiments, the multilayer film can have a thickness of 15 μm to 500 μm, or 15 μm to 260 μm. In other embodiments, the multilayer film may have an overall thickness of 15 μm to 200 μm, 15 μm to 150 μm, 15 μm to 100 μm, 15 μm to 50 μm, 50 μm to 500 μm, 50 μm to 260 μm, 50 μm to 200 μm, 50 μm to 150 μm, 50 μm to 100 μm, 100 μm to 500 μm, 100 μm to 260 μm, 100 μm to 200 μm, 100 μm to 150 μm, 150 μm to 500 μm, 150 μm to 260 μm, 150 μm to 200 μm, 200 μm to 500 μm, 200 μm to 260 μm, or 260 μm to 500 μm.
[0033] Multilayer films of the present disclosure may have an overall density that depends on a number of factors including, for example, the number of layers in the multilayer film, the composition of the layers in the multilayer film, the desired properties of the multilayer film, the desired end use of the film, the manufacturing process for the multilayer film, etc. In an embodiment, the multilayer film has an overall density of at least 0.925 grams per cubic centimeter (g / cm 3 In another embodiment, the multilayer film may have an overall density of 0.925 g / cm 3 ~0.960g / cm 3 , 0.925g / cm 3 ~0.940g / cm 3 , 0.925g / cm 3 ~0.935g / cm 3 , 0.925g / cm 3 ~0.930g / cm 3 , 0.930g / cm 3 ~0.940g / cm 3 , 0.930g / cm 3 ~0.935g / cm 3 , or 0.935 g / cm3 ~0.940g / cm 3 It could be.
[0034] The multilayer films of the present disclosure may have relatively good dart strength when measured according to ASTM D1709 Method A. In an embodiment, the multilayer films may have a dart drop impact of at least 300 grams when measured according to ASTM D1709 Method A. In other embodiments, the multilayer films may have a dart drop impact of 600 grams to 2000 grams, 600 grams to 1500 grams, 600 grams to 1000 grams, 700 grams to 2000 grams, 700 grams to 1500 grams, 700 grams to 1000 grams, 1000 grams to 2000 grams, 1000 grams to 1500 grams, or 1500 grams to 2000 grams when measured according to ASTM D1709 Method A. In further embodiments, the multilayer films of the present disclosure may have relatively good dart strength when measured according to ASTM D1709 Method B. In embodiments, the multilayer film may have a dart drop impact of at least 300 grams when measured according to ASTM D1709 Method B. In other embodiments, the multilayer film may have a dart drop impact of 400 grams to 2000 grams, 400 grams to 1500 grams, 400 grams to 1000 grams, 700 grams to 2000 grams, 700 grams to 1500 grams, 700 grams to 1000 grams, 1000 grams to 2000 grams, 1000 grams to 1500 grams, or 1500 grams to 2000 grams when measured according to ASTM D1709 Method A.
[0035] The multilayer films of the present disclosure may have a cross-direction tensile creep of less than 50% when measured according to ASTM 2990. In other embodiments, the multilayer films may have a tensile creep of less than 40% or less than 30% when measured according to ASTM 2990.
[0036] The multilayer films of the present disclosure have a compressibility of 40 ft*lbf / in when measured according to the test method described later in this disclosure. 3In other embodiments, the multilayer film may have a puncture energy at break of greater than 50 ft*lbf / in when measured according to the test method described later in this disclosure. 3 or 60ft*lbf / in 3 The puncture energy at break may be greater than or equal to 100 .mu.m.
[0037] The multilayer films of the present disclosure may have an average secant modulus in the machine direction of at least 50,000 psi, as measured according to ASTM D882. In other embodiments, the multilayer films may have an average secant modulus in the machine direction of at least 55,000 psi or 60,000 psi, as measured according to ASTM D882. The multilayer films of the present disclosure may have an average secant modulus in the cross direction of at least 55,000 psi, as measured according to ASTM D882. In other embodiments, the multilayer films may have an average secant modulus in the cross direction of at least 60,000 psi or 70,000 psi, as measured according to ASTM D882.
[0038] Core layer As previously mentioned, the multilayer films of the present disclosure may include a core layer. In a multilayer film designated as a three-layer structure, A / B / C, the core layer may be designated as B. In some embodiments, the core layer may be referred to as the "first layer." In further embodiments, the core layer may be in direct contact with one or both of the second and third layers.
[0039] The core layer of the multilayer film of the present disclosure can have a variety of thicknesses. The thickness of the core layer can depend on a number of factors including, for example, the composition of the core layer, the desired overall properties of the multilayer film, the desired end use of the multilayer film, the manufacturing process of the multilayer film, etc. In embodiments, the core layer can have a thickness of from 0.5 micrometers (μm or microns) to 60 μm. In other embodiments, the second layer may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0040] The core layer of the multilayer film disclosed herein may comprise 5% to 90% by weight of the total weight of the multilayer film. In some embodiments, the core layer may comprise 5% to 70%, 5% to 60%, 5% to 50%, 5% to 40%, 5% to 30%, 5% to 20%, 5% to 10%, 10% to 40%, 10% to 30%, 10% to 20%, 20% to 40%, 20% to 30%, or 30% to 40% by weight of the total weight of the multilayer film.
[0041] The core layer may include a polyethylene composition, which is described in more detail later in this disclosure. The polyethylene composition may exhibit a balance of toughness and tear strength, which allows for multilayer films with improved abuse characteristics (i.e., dart, puncture energy, tear). For example, the polyethylene composition of the present disclosure may have high dart strength at relatively high density. As described in more detail later in this disclosure, such improved properties may include improved creep, elongation, and toughness. These improved properties may further allow for multilayer films that use less material ("downgauge," i.e., use a thinner film thickness) or may be produced using more simplified processes, as compared to conventional multilayer films.
[0042] In one or more embodiments, the core layer may comprise at least 50% by weight of the polyethylene composition based on the total weight of the core layer. In some embodiments, the core layer may comprise about 10% to about 100% by weight, about 10% to about 80% by weight, about 10% to about 60% by weight, about 10% to about 40% by weight, about 10% to about 20% by weight, about 20% to about 100% by weight, about 20% to about 80% by weight, about 20% to about 60% by weight, about 20% to about 40% by weight, about 40% to about 100% by weight, about 40% to about 80% by weight, about 40% to about 60% by weight, about 60% to about 100% by weight, about 60% to about 80% by weight, or about 80% to about 100% by weight of the polyethylene composition based on the total weight of the core layer.
[0043] In some embodiments, the core layer may include a blend of the polyethylene composition with one or more additional materials. In embodiments, the blend may include high density polyethylene (HDPE), low density polyethylene (LDPE), or a combination.
[0044] Optionally, in some embodiments, the core layer may include high density polyethylene (HDPE). High density polyethylene may be incorporated into the core layer to increase the stiffness of the core layer. In some applications, it may be important for the multilayer film to have sufficient stiffness, as indicated, for example, by the tensile modulus, to prevent deformation and to prevent breakage.
[0045] In an embodiment, the high density polyethylene has a viscosity of 0.935 g / cm as measured according to ASTM D792. 3 ~Maximum approx. 0.980g / cm 3 In another embodiment, the high density polyethylene has a density of 0.935 g / cm 3 ~0.970g / cm 3 , 0.935g / cm 3 ~0.960g / cm 3 , 0.935g / cm 3 ~0.950g / cm 3 , 0.935g / cm 3~0.940g / cm 3 , 0.940g / cm 3 ~0.980g / cm 3 , 0.940g / cm 3 ~0.970g / cm 3 , 0.940g / cm 3 ~0.960g / cm 3 , 0.940g / cm 3 ~0.950g / cm 3 , 0.950g / cm 3 ~0.980g / cm 3 , 0.950g / cm 3 ~0.970g / cm 3 , 0.950g / cm 3 ~0.960g / cm 3 , 0.960g / cm 3 ~0.980g / cm 3 , 0.960g / cm 3 ~0.970g / cm 3 , 0.970g / cm 3 ~0.980g / cm 3 It could be.
[0046] In one or more embodiments, the core layer may comprise a high density polyethylene having a melt index (I2) of 0.1 grams per 10 minutes (g / 10 min) to 10.0 g / 10 min, as measured according to ASTM D1238 at a load of 2.16 kg and a temperature of 190° C. It is also contemplated that the melt index (I2) of the high density polyethylene may be 0.1 g / 10 min to 5.0 g / 10 min, 0.1 g / 10 min to 1.0 g / 10 min, 1.0 g / 10 min to 10.0 g / 10 min, 1.0 g / 10 min to 5.0 g / 10 min, or 5.0 g / 10 min to 10.0 g / 10 min.
[0047] Various methodologies are contemplated for the production of high density polyethylene. For example, high density polyethylene resins may be made using Ziegler-Natta catalyst systems, chromium catalysts, or single-site catalysts, including but not limited to bismetallocene catalysts and constrained geometry catalysts.
[0048] In one or more embodiments, the core layer may comprise up to 50% by weight of high density polyethylene, based on the total weight of the core layer. In some embodiments, the core layer may comprise about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight of high density polyethylene, based on the total weight of the core layer.
[0049] Optionally, in some embodiments, the core layer may comprise low density polyethylene (LDPE). In one or more embodiments, the low density polyethylene may have a melt index of 0.1 g / 10 min to 10.0 g / 10 min, as measured according to ASTM D1238 at a load of 2.16 kg and a temperature of 190° C. In other embodiments, the low density polyethylene may have a melt index of 0.1 g / 10 min to 5.0 g / 10 min, or 0.5 g / 10 min to 5.0 g / 10 min, or 0.5 g / 10 min to 2.0 g / 10 min. In embodiments, the low density polyethylene may have a melt index of 0.916 g / cm 3 or less, as measured according to ASTM D792. 3 ~0.935g / cm 3 In another embodiment, the low density polyethylene may have a density of 0.916 g / cm 3 ~0.925g / cm 3 The density of the sintered body may be 0.01 to 0.01.
[0050] In one or more embodiments, the core layer may comprise less than 50% by weight of low density polyethylene, based on the total weight of the core layer. In some embodiments, the core layer may comprise about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight of low density polyethylene, based on the total weight of the core layer.
[0051] outer layer As previously mentioned, the multilayer films of the present disclosure may include an outer layer, which may also be referred to as a "skin layer." The outer layer may include a second layer and a third layer. In a three-layer structure, a multilayer film designated as A / B / C, the outer layers may be designated as A and C. The second layer may be designated as A. The third layer may be designated as C. In further embodiments, the second layer, the third layer, or both may be the outermost layer of the multilayer film. In further embodiments, the second layer, the third layer, or both may be in direct contact with the first layer.
[0052] The second layer, the third layer, or both of the multilayer film may each have a thickness of 0.5 micrometers (μm or microns) to 60 μm. In other embodiments, the second layer, the third layer, or both of the multilayer film may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0053] The second layer, the third layer, or both of the multilayer film may comprise 5% to 90% by weight of the total weight of the multilayer film. In some embodiments, the second layer, the third layer, or both of the multilayer film of Exemplary Embodiment 1 may comprise 10% to 90%, 20% to 80%, 30% to 60%, or 30% to 40% by weight of the total weight of the multilayer film.
[0054] In various embodiments, the second layer, the third layer, or both may include one or more materials that provide properties to the multilayer film that aid in orientation, processability, etc. In some embodiments, the second layer and the third layer may include the same material. In other embodiments, the second layer and the third layer may include different materials. In embodiments, the second layer may include a first polyolefin. In embodiments, the third layer may include a second polyolefin. The first polyolefin and the second polyolefin may be the same or different in composition. In some embodiments, the first polyolefin, the second polyolefin, or both may be a polyolefin having a viscosity of 0.900 g / cm or less. 3 ~0.970g / cm 3 In some embodiments, the polyethylene of the second layer, the third layer, or both may include one or more of LLDPE, HDPE, MDPE, and LDPE.
[0055] In one or more embodiments, the second layer, the third layer, or both, have a modulus of elasticity of 0.905 g / cm as measured according to ASTM D792. 3 ~0.930g / cm 3 In another embodiment, the linear low density polyethylene may include a linear low density polyethylene (LLDPE) having a density of 0.905 g / cm. 3 ~0.925g / cm 3 , 0.905g / cm 3 ~0.920g / cm 3 , 0.905g / cm 3 ~0.915g / cm 3 , 0.905g / cm 3 ~0.910g / cm 3 , 0.910g / cm 3 ~0.930g / cm 3 , 0.910g / cm 3 ~0.925g / cm 3 , 0.910g / cm 3 ~0.920g / cm 3 , 0.910g / cm 3 ~0.915g / cm 3 , 0.915g / cm 3~0.930g / cm 3 , 0.915g / cm 3 ~0.925g / cm 3 , 0.915g / cm 3 ~0.920g / cm 3 , 0.920g / cm 3 ~0.930g / cm 3 , 0.920g / cm 3 ~0.925g / cm 3 , 0.925g / cm 3 ~0.930g / cm 3 It could be.
[0056] In one or more embodiments, the second layer, the third layer, or both may include a linear low density polyethylene (LLDPE) having a melt index (I2) of 0.2 grams per 10 minutes (g / 10 min) to 2.0 g / 10 min, as measured according to ASTM D1238. It is also contemplated that the melt index (I2) of the linear low density polyethylene can be from 0.2 g / 10 min to 1.5 g / 10 min, from 0.2 g / 10 min to 1.0 g / 10 min, from 0.2 g / 10 min to 0.5 g / 10 min, from 0.5 g / 10 min to 2.0 g / 10 min, from 0.5 g / 10 min to 1.5 g / 10 min, from 0.5 g / 10 min to 1.0 g / 10 min, from 1.0 g / 10 min to 2.0 g / 10 min, from 1.0 g / 10 min to 1.5 g / 10 min, or from 1.5 g / 10 min to 2.0 g / 10 min.
[0057] According to embodiments, the linear low density polyethylene may have a molecular weight distribution, expressed as the ratio of weight average molecular weight to number average molecular weight (Mw / Mn), in the range of 3.5 to 5.5. In additional embodiments, the linear low density polyethylene may have a molecular weight distribution in the range of 3.5 to 4.5 or 4.5 to 5.5.
[0058] According to one or more additional embodiments, the linear low density polyethylene may have a zero shear viscosity ratio of 1.2 to 3.0, as measured according to the test methods described herein. In other embodiments, the linear low density polyethylene may have a zero shear viscosity ratio of 1.2 to 2.5, 1.2 to 2.0, 2.0 to 3.0, 2.0 to 2.5, or 2.5 to 3.0.
[0059] Various methodologies are contemplated for the production of linear low density polyethylene. For example, linear low density polyethylene resins may be made using Ziegler-Natta catalyst systems, resins made using single-site catalysts, including but not limited to bismetallocene catalysts and constrained geometry catalysts, resins made using post-metallocene molecular catalysts. Linear low density polyethylene resins may include linear, substantially linear, or heterogeneous polyethylene copolymers or homopolymers. Linear low density polyethylene resins contain less long chain branching than LDPE and include substantially linear polyethylenes as further defined in U.S. Pat. Nos. 5,272,236, 5,278,272, 5,582,923, and 5,733,155, homogeneously branched linear ethylene polymer compositions such as those in U.S. Pat. No. 3,645,992, heterogeneously branched ethylene polymers such as those prepared according to the process disclosed in U.S. Pat. No. 4,076,698, and blends thereof (such as those disclosed in U.S. Pat. No. 3,914,342 or U.S. Pat. No. 5,854,045). Linear low density polyethylene resins may be made by gas phase, solution phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.
[0060] In one or more embodiments, the second layer, the third layer, or both, may comprise 0% to 100% by weight of linear low density polyethylene, based on the total weight of the respective layer. In some embodiments, the second layer, the third layer, or both, may comprise about 50% to about 100%, about 50% to about 80%, about 50% to about 60%, about 60% to about 100%, about 60% to about 80%, or about 80% to about 100% by weight of LLDPE, based on the total weight of the respective layer.
[0061] Optionally, in some embodiments, the second layer, the third layer, or both have a modulus of elasticity of 0.935 g / cm as measured according to ASTM D792. 3~Maximum approx. 0.980g / cm 3 In another embodiment, the density of the high density polyethylene may be 0.935 g / cm. 3 ~0.970g / cm 3 , 0.935g / cm 3 ~0.960g / cm 3 , 0.935g / cm 3 ~0.950g / cm 3 , 0.935g / cm 3 ~0.940g / cm 3 , 0.940g / cm 3 ~0.980g / cm 3 , 0.940g / cm 3 ~0.970g / cm 3 , 0.940g / cm 3 ~0.960g / cm 3 , 0.940g / cm 3 ~0.950g / cm 3 , 0.950g / cm 3 ~0.980g / cm 3 , 0.950g / cm 3 ~0.970g / cm 3 , 0.950g / cm 3 ~0.960g / cm 3 , 0.960g / cm 3 ~0.980g / cm 3 , 0.960g / cm 3 ~0.970g / cm 3 , or 0.970 g / cm 3 ~0.980g / cm 3 It could be.
[0062] In one or more embodiments, the second layer, the third layer, or both may comprise a high density polyethylene having a melt index (I2) of 0.1 grams per 10 minutes (g / 10 min) to 10.0 g / 10 min, as measured according to ASTM D1238 at a load of 2.16 kg and a temperature of 190° C. It is also contemplated that the melt index (I2) of the high density polyethylene may be 0.1 g / 10 min to 5.0 g / 10 min, 0.1 g / 10 min to 1.0 g / 10 min, 1.0 g / 10 min to 10.0 g / 10 min, 1.0 g / 10 min to 5.0 g / 10 min, or 5.0 g / 10 min to 10.0 g / 10 min.
[0063] Various methodologies are contemplated for the production of high density polyethylene. For example, high density polyethylene resins may be made using Ziegler-Natta catalyst systems, chromium catalysts, or single-site catalysts, including but not limited to bismetallocene catalysts and constrained geometry catalysts.
[0064] In one or more embodiments, the second layer, the third layer, or both may comprise up to 50% by weight of high density polyethylene, based on the total weight of the respective layer. In some embodiments, the second layer, the third layer, or both may comprise about 0% to about 50%, about 0% to about 40%, about 0% to about 20%, about 20% to about 50%, about 20% to about 40%, or about 40% to about 50% by weight of high density polyethylene, based on the total weight of the respective layer.
[0065] Optionally, in some embodiments, the second layer, the third layer, or both may comprise medium density polyethylene (MDPE). In one or more embodiments, the medium density polyethylene may have a melt index of 0.1 g / 10 min to 10.0 g / 10 min, as measured according to ASTM D1238 at a load of 2.16 kg and a temperature of 190° C. In other embodiments, the medium density polyethylene may have a melt index of 0.1 g / 10 min to 5.0 g / 10 min, or 0.5 g / 10 min to 5.0 g / 10 min, or 0.5 g / 10 min to 2.0 g / 10 min. In embodiments, the medium density polyethylene may have a melt index of 0.924 g / cm, as measured according to ASTM D792. 3 ~0.942g / cm 3 In another embodiment, the low density polyethylene may have a density of 0.924 g / cm 3 ~0.936g / cm 3 The density of the sintered body may be 0.01 to 0.01.
[0066] In one or more embodiments, the second layer, the third layer, or both may comprise less than 50% by weight of medium density polyethylene, based on the total weight of the respective layer. In some embodiments, the second layer, the third layer, or both may comprise less than 50% by weight of medium density polyethylene, based on the total weight of the respective layer. In some embodiments, the second layer, the third layer, or both may comprise less than 50% by weight of medium density polyethylene, based on the total weight of the respective layer. It may contain 0% to about 20% by weight, about 20% to about 100% by weight, about 20% to about 80% by weight, about 20% to about 60% by weight, about 20% to about 40% by weight, about 40% to about 100% by weight, about 40% to about 80% by weight, about 40% to about 60% by weight, about 60% to about 100% by weight, about 60% to about 80% by weight, or about 80% to about 100% by weight of MDPE.
[0067] The second layer, the third layer, or both may comprise a polyethylene composition, which is described in more detail later in this disclosure. The polyethylene composition may exhibit a balance of toughness and tear strength, which allows for multilayer films with improved abuse characteristics (i.e., dart, puncture energy, tear). For example, the polyethylene composition of the present disclosure may have high dart strength at relatively high density. As described in more detail later, such improved properties may include improved creep, elongation, and toughness. These improved properties may further allow for multilayer films that use less material ("downgauge," i.e., use a thinner film thickness) or can be produced using more simplified processes, as compared to conventional multilayer films.
[0068] In one or more embodiments, the second layer, the third layer, or both may comprise from about 0% to about 100% by weight, from about 0% to about 80% by weight, from about 0% to about 60% by weight, from about 0% to about 0% by weight, from about 0% to about 20% by weight, from about 10% to about 100% by weight, from about 10% to about 80% by weight, from about 10% to about 60% by weight, from about 10% to about 40% by weight, from about 10% to about 50% by weight, from about 10% to about 60% by weight, from about 10% to about 80% by weight, from about 10% to about 90% by weight, from about 10% to about 100% by weight, from about 10% to about 80% by weight, from about 10% to about 60% by weight, from about 10% to about 40% by weight, from about 10% to about 10 ... The polyethylene composition may comprise from about 20% to about 20% by weight, from about 20% to about 100% by weight, from about 20% to about 80% by weight, from about 20% to about 60% by weight, from about 20% to about 40% by weight, from about 40% to about 100% by weight, from about 40% to about 80% by weight, from about 40% to about 60% by weight, from about 60% to about 100% by weight, from about 60% to about 80% by weight, or from about 80% to about 100% by weight.
[0069] Optionally, in some embodiments, the second layer, the third layer, or both may comprise low density polyethylene (LDPE). In one or more embodiments, the low density polyethylene may have a melt index of 0.1 g / 10 min to 10.0 g / 10 min, as measured according to ASTM D1238 at a load of 2.16 kg and a temperature of 190° C. In other embodiments, the low density polyethylene may have a melt index of 0.1 g / 10 min to 5.0 g / 10 min, or 0.5 g / 10 min to 5.0 g / 10 min, or 0.5 g / 10 min to 2.0 g / 10 min. In embodiments, the low density polyethylene may have a melt index of 0.916 g / cm, as measured according to ASTM D792. 3 ~0.935g / cm 3 In another embodiment, the low density polyethylene may have a density of 0.916 g / cm 3 ~0.925g / cm 3 The density of the sintered body may be 0.01 to 0.01.
[0070] In one or more embodiments, the second layer, the third layer, or both may comprise less than 50% by weight of low density polyethylene, based on the total weight of the respective layer. In some embodiments, the second layer, the third layer, or both may comprise about 0% to about 50%, about 0% to about 40%, about 0% to about 20%, about 20% to about 50%, about 20% to about 40%, or about 40% to about 50% by weight of low density polyethylene, based on the total weight of the respective layer.
[0071] Additional Layers As previously mentioned, in some embodiments, the multilayer film may include one or more additional layers. In some embodiments, the multilayer films of the present disclosure may include up to 11, 13, 15, or more layers.
[0072] The one or more additional layers may include one or more materials that impart properties to the multilayer film that aid in stretching, processability, stiffness, etc. In embodiments, the one or more additional layers may include one or more polyolefins. In some embodiments, the one or more polyolefins include 3~0.970g / cm 3 In some embodiments, the one or more polyethylenes of the one or more additional layers may include LLDPE, HDPE, MDPE, LDPE, polyethylene compositions, and combinations.
[0073] In some embodiments, the multilayer film may optionally include tie layers to facilitate adhesion between the layers. In some embodiments, the tie layers may be disposed between the core layer and each outer layer. In a multilayer film designated as A / Tie 1 / B / Tie 2 / C, the core layer may be designated as B, the outer layers may be designated as A and C, and the tie layers may be designated as Tie 1 and Tie 2. The second layer may be designated as A. The third layer may be designated as C. In further embodiments, the second layer, the third layer, or both may be the outermost layers of the multilayer film. In further embodiments, the first tie layer (Tie 1) may be in direct contact with one or both of the first layer and the second layer. In further embodiments, the second tie layer (Tie 2) may be in direct contact with one or both of the first layer and the third layer. In some such embodiments, the tie layers may include maleic anhydride grafted polyethylene or other functionalized resins known to be useful as tie layers. A suitable commercially available example of maleic anhydride grafted polyethylene is AMPLIFY™ TY1057 from The Dow Chemical Company (Midland, Mich.), although others known to those skilled in the art may also be used.
[0074] In some embodiments, the multilayer film may optionally include a barrier. Suitable barrier layers may be selected from layers comprising ethylene vinyl alcohol copolymers, cyclic olefin copolymers, polyvinyl acetate, or blends of one or more of these polymers with polyethylene, polyvinyl alcohol, or polyamide.
[0075] Exemplary embodiment 1 As previously discussed, there is a need for multilayer films that exhibit physical properties such as dart / bag drop resistance, puncture resistance, tear resistance, and creep resistance that meet customer and industry requirements. In some embodiments, these multilayer films may maintain physical properties at reduced thicknesses that still meet customer and industry requirements.
[0076] Reference is now made to an embodiment of the multilayer film described herein, referred to herein as "exemplary embodiment 1." Exemplary embodiment 1 may include a first layer comprising a polyethylene composition, a second layer comprising a first linear low density polyethylene, and a third layer comprising a second linear low density polyethylene. The core layer of exemplary embodiment 1 may include a polyethylene composition, which is described in more detail later in this disclosure. While utilized in a film, the polyethylene composition may exhibit a balance of toughness and stiffness, thereby enabling the multilayer film of exemplary embodiment 1 to have improved abuse characteristics (i.e., dart, puncture energy, tear). For example, utilization of the polyethylene composition of the present disclosure provides a core layer that exhibits relatively high dart strength at a relatively high density. These improved properties may further enable the multilayer film embodiment of exemplary embodiment 1 to use less material ("downgauge," i.e., use a thinner film thickness) or be produced using a more simplified process, as compared to conventional multilayer films.
[0077] The multilayer film of exemplary embodiment 1 can have a variety of thicknesses. In further embodiments, the multilayer film of exemplary embodiment 1 can have a thickness of less than 150 micrometers (μm or microns). In other embodiments, the multilayer film can have a thickness of 15 μm to 120 μm. In other embodiments, the multilayer film can have an overall thickness of 25 μm to 100 μm, 25 μm to 75 μm, 25 μm to 50 μm, 50 μm to 150 μm, 50 μm to 100 μm, 50 μm to 75 μm, 75 μm to 150 μm, 75 μm to 100 μm, or 100 μm to 150 μm.
[0078] In an embodiment, the multilayer film of exemplary embodiment 1 has a tensile strength of at least 0.925 grams per cubic centimeter (g / cm 3 In another embodiment, the multilayer film of exemplary embodiment 1 may have an overall density of 0.925 g / cm 3 ~0.940g / cm 3 , 0.925g / cm 3 ~0.935g / cm 3 , 0.925g / cm 3 ~0.930g / cm 3 , 0.930g / cm 3 ~0.940g / cm 3 , 0.930g / cm 3 ~0.935g / cm 3 , or 0.935 g / cm 3 ~0.940g / cm 3 It could be.
[0079] In an embodiment, the multilayer film of exemplary embodiment 1 may have relatively good dart strength when measured according to ASTM D1709 Method B. In an embodiment, the multilayer film of exemplary embodiment 1 may have a dart drop impact of at least 400 grams when measured according to ASTM D1709 Method B. In other embodiments, the multilayer film of exemplary embodiment 1 may have a dart drop impact of 400 grams to 2000 grams, 400 grams to 1500 grams, 400 grams to 1000 grams, 700 grams to 2000 grams, 700 grams to 1500 grams, 700 grams to 1000 grams, 1000 grams to 2000 grams, 1000 grams to 1500 grams, or 1500 grams to 2000 grams when measured according to ASTM D1709 Method A.
[0080] The multilayer film of exemplary embodiment 1 may have an average secant modulus in the machine direction of at least 50,000 psi, as measured according to ASTM D882. In other embodiments, the multilayer film may have an average secant modulus in the machine direction of at least 55,000 psi or 60,000 psi, as measured according to ASTM D882. The multilayer film of the present disclosure may have an average secant modulus in the cross direction of at least 55,000 psi, as measured according to ASTM D882. In other embodiments, the multilayer film may have an average secant modulus in the cross direction of at least 60,000 psi or 70,000 psi, as measured according to ASTM D882.
[0081] The core layer of the multilayer film of exemplary embodiment 1 may have a thickness of 0.5 micrometers (μm or microns) to 60 μm. In other embodiments, the core layer may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0082] The core layer of the multilayer film of exemplary embodiment 1 may comprise 10% to 80% by weight of the total weight of the multilayer film of exemplary embodiment 1. In some embodiments, the core layer may comprise 10% to 60% by weight, 10% to 40% by weight, 10% to 30% by weight, 10% to 20% by weight, 20% to 80% by weight, 20% to 40% by weight, 20% to 30% by weight, 30% to 80% by weight, 30% to 60% by weight, or 30% to 40% by weight of the total weight of the multilayer film of exemplary embodiment 1.
[0083] In one or more embodiments, the core layer of exemplary embodiment 1 may comprise at least 10 wt% of the polyethylene composition, based on the total weight of the core layer. In some embodiments, the core layer may comprise about 10 wt% to about 100 wt%, about 10 wt% to about 80 wt%, about 10 wt% to about 60 wt%, about 10 wt% to about 40 wt%, about 10 wt% to about 20 wt%, about 20 wt% to about 100 wt%, about 20 wt% to about 80 wt%, about 20 wt% to about 60 wt%, about 20 wt% to about 40 wt%, about 40 wt% to about 100 wt%, about 40 wt% to about 80 wt%, about 40 wt% to about 60 wt%, about 60 wt% to about 100 wt%, about 60 wt% to about 80 wt%, or about 80 wt% to about 100 wt% of the polyethylene composition, based on the total weight of the core layer.
[0084] Optionally, in some embodiments, the core layer of exemplary embodiment 1 may include low density polyethylene (LDPE). In one or more embodiments, the core layer may include less than 50% by weight of low density polyethylene, based on the total weight of the core layer. In some embodiments, the core layer of exemplary embodiment 1 may include about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight of low density polyethylene, based on the total weight of the core layer.
[0085] The second layer, the third layer, or both of the multilayer film of exemplary embodiment 1 may each have a thickness of 0.5 micrometers (μm or microns) to 60 μm. In other embodiments, the second layer, the third layer, or both of the multilayer film of exemplary embodiment 1 may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0086] The second layer, the third layer, or both of the multilayer film of exemplary embodiment 1 may comprise 10% to 90% by weight of the total weight of the multilayer film of exemplary embodiment 1. In some embodiments, the second layer, the third layer, or both of the multilayer film of exemplary embodiment 1 may comprise 20% to 80% by weight, 30% to 60% by weight, or 30% to 40% by weight of the total weight of the multilayer film of exemplary embodiment 1.
[0087] In one or more embodiments, the second layer, the third layer, or both, may comprise greater than 50% by weight linear low density polyethylene, based on the total weight of the respective layer. In some embodiments, the second layer, the third layer, or both, may comprise about 50% to about 100%, about 50% to about 80%, about 50% to about 60%, about 60% to about 100%, about 60% to about 80%, or about 80% to about 100% by weight LLDPE, based on the total weight of the respective layer.
[0088] Optionally, in some embodiments, the second layer, the third layer, or both of Exemplary Embodiment 1 may include low density polyethylene (LDPE). In one or more embodiments, the second layer, the third layer, or both may include less than 50% by weight of low density polyethylene, based on the total weight of the respective layer. In some embodiments, the second layer, the third layer, or both of Exemplary Embodiment 1 may include about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight of low density polyethylene, based on the total weight of the respective layer.
[0089] Exemplary embodiment 2 As previously discussed, there is a need for multilayer films that exhibit physical properties such as dart / bag drop resistance, puncture resistance, tear resistance, and creep resistance that meet customer and industry requirements. In some embodiments, these multilayer films may maintain physical properties at reduced thicknesses that still meet customer and industry requirements.
[0090] Reference is now made to an embodiment of the multilayer film described herein, referred to herein as "exemplary embodiment 2." Exemplary embodiment 2 may include a first layer comprising a polyethylene composition and a high density polyethylene, a second layer comprising a first linear low density polyethylene, and a third layer comprising a second linear low density polyethylene. The core layer of exemplary embodiment 2 may include a polyethylene composition, which is described in more detail below in this disclosure. The polyethylene composition may exhibit a balance of toughness and tear strength, which allows the multilayer film of exemplary embodiment 2 to exhibit improved abuse characteristics (i.e., dart, puncture energy, tear). For example, utilization of the polyethylene composition of the present disclosure provides a core layer that exhibits relatively high dart strength at a relatively high density. These improved properties may further enable the multilayer film embodiment of exemplary embodiment 2 to use less material ("downgauge," i.e., use a thinner film thickness) or be produced using a more simplified process, as compared to conventional multilayer films.
[0091] The multilayer film of exemplary embodiment 2 can have a variety of thicknesses. In further embodiments, the multilayer film of exemplary embodiment 2 can have a thickness of less than 500 micrometers (μm or microns). In other embodiments, the multilayer film can have a thickness of 15 μm to 500 μm, or 15 μm to 260 μm. In other embodiments, the multilayer film may have an overall thickness of 15 μm to 200 μm, 15 μm to 150 μm, 15 μm to 100 μm, 15 μm to 50 μm, 50 μm to 500 μm, 50 μm to 260 μm, 50 μm to 200 μm, 50 μm to 150 μm, 50 μm to 100 μm, 100 μm to 500 μm, 100 μm to 260 μm, 100 μm to 200 μm, 100 μm to 150 μm, 150 μm to 500 μm, 150 μm to 260 μm, 150 μm to 200 μm, 200 μm to 500 μm, 200 μm to 260 μm, or 260 μm to 500 μm.
[0092] In an embodiment, the multilayer film of exemplary embodiment 1 has a tensile strength of at least 0.925 grams per cubic centimeter (g / cm 3 In another embodiment, the multilayer film of exemplary embodiment 2 may have an overall density of 0.925 g / cm 3 ~0.940g / cm 3 , 0.925g / cm 3 ~0.935g / cm 3 , 0.925g / cm 3 ~0.930g / cm 3 , 0.930g / cm 3 ~0.940g / cm 3 , 0.930g / cm 3 ~0.935g / cm 3 , or 0.935 g / cm 3 ~0.940g / cm 3 It could be.
[0093] In an embodiment, the multilayer film of exemplary embodiment 2 may have a dart drop impact of at least 600 grams when measured according to ASTM D1709 Method A. In other embodiments, the multilayer film of exemplary embodiment 2 may have a dart drop impact of 600 grams to 2000 grams, 600 grams to 1500 grams, 600 grams to 1000 grams, 700 grams to 2000 grams, 700 grams to 1500 grams, 700 grams to 1000 grams, 1000 grams to 2000 grams, 1000 grams to 1500 grams, or 1500 grams to 2000 grams when measured according to ASTM D1709 Method A. In further embodiments, the multilayer film of exemplary embodiment 2 may have a relatively good dart strength when measured according to ASTM D1709 Method B. In an embodiment, the multilayer film of exemplary embodiment 2 may have a dart drop impact of at least 400 grams when measured according to ASTM D1709 Method B. In other embodiments, the multilayer film of exemplary embodiment 2 may have a dart drop impact of 400 grams to 2000 grams, 400 grams to 1500 grams, 400 grams to 1000 grams, 700 grams to 2000 grams, 700 grams to 1500 grams, 700 grams to 1000 grams, 1000 grams to 2000 grams, 1000 grams to 1500 grams, or 1500 grams to 2000 grams, as measured according to ASTM D1709 Method A.
[0094] The multilayer film of exemplary embodiment 2 may have a cross-direction tensile creep of less than 50% when measured according to ASTM 2990. In other embodiments, the multilayer film of exemplary embodiment 2 may have a tensile creep of less than 40% or less than 30% when measured according to ASTM 2990.
[0095] The multilayer film of exemplary embodiment 2 has a compressibility of 30 ft*lbf / in when measured according to the test method described later in this disclosure. 3 In other embodiments, the multilayer film of exemplary embodiment 2 may have a puncture energy at break of greater than 40 ft*lbf / in when measured according to the test method described later in this disclosure.3 or 50ft*lbf / in 3 The puncture energy at break may be greater than or equal to 100 .mu.m.
[0096] The multilayer film of exemplary embodiment 2 may have an average secant modulus in the machine direction of at least 50,000 psi, as measured according to ASTM D882. In other embodiments, the multilayer film may have an average secant modulus in the machine direction of at least 55,000 psi or 60,000 psi, as measured according to ASTM D882. The multilayer film of the present disclosure may have an average secant modulus in the cross direction of at least 55,000 psi, as measured according to ASTM D882. In other embodiments, the multilayer film may have an average secant modulus in the cross direction of at least 60,000 psi or 70,000 psi, as measured according to ASTM D882.
[0097] The core layer of the multilayer film of exemplary embodiment 2 can have a thickness of 0.5 micrometers (μm or microns) to 60 μm. In other embodiments, the second layer can have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0098] The core layer of the multilayer film of exemplary embodiment 2 may comprise 5% to 60% by weight of the total weight of the multilayer film of exemplary embodiment 2. In some embodiments, the core layer may comprise 5% to 30% by weight, 5% to 20% by weight, 5% to 10% by weight, 10% to 40% by weight, 10% to 30% by weight, 10% to 20% by weight, 20% to 40% by weight, 20% to 30% by weight, or 30% to 40% by weight of the total weight of the multilayer film of exemplary embodiment 2.
[0099] In one or more embodiments, the core layer of exemplary embodiment 2 may comprise at least 50 wt% of the polyethylene composition, based on the total weight of the core layer. In some embodiments, the core layer may comprise from about 10 wt% to about 100 wt%, from about 10 wt% to about 80 wt%, from about 10 wt% to about 60 wt%, from about 10 wt% to about 40 wt%, from about 10 wt% to about 20 wt%, from about 20 wt% to about 100 wt%, from about 20 wt% to about 80 wt%, from about 20 wt% to about 60 wt%, from about 20 wt% to about 40 wt%, from about 40 wt% to about 100 wt%, from about 40 wt% to about 80 wt%, from about 40 wt% to about 60 wt%, from about 60 wt% to about 100 wt%, from about 60 wt% to about 80 wt%, or from about 80 wt% to about 100 wt% of the polyethylene composition, based on the total weight of the core layer.
[0100] In an embodiment, the core layer of exemplary embodiment 2 may include high density polyethylene (HDPE). In one or more embodiments, the core layer may include up to 50% by weight of high density polyethylene, based on the total weight of the core layer. In some embodiments, the core layer may include about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight of high density polyethylene, based on the total weight of the core layer.
[0101] The second layer, the third layer, or both of the multilayer film of exemplary embodiment 2 may each have a thickness of 0.5 micrometers (μm or microns) to 60 μm. In other embodiments, the second layer, the third layer, or both of the multilayer film of exemplary embodiment 1 may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0102] The second layer, the third layer, or both of the multilayer film of exemplary embodiment 2 may comprise 5% to 40% by weight of the total weight of the multilayer film of exemplary embodiment 2. In some embodiments, the second layer, the third layer, or both of the multilayer film of exemplary embodiment 2 may comprise 5% to 30%, 5% to 20%, 5% to 10%, 10% to 40%, 10% to 30%, 10% to 20%, 20% to 40%, 20% to 30%, or 30% to 40% by weight of the total weight of the multilayer film of exemplary embodiment 2.
[0103] In one or more embodiments, the second layer, the third layer, or both of exemplary embodiment 2 may include about 0 to about 100% by weight linear low density polyethylene, based on the total weight of the respective layer. In some embodiments, the second layer, the third layer, or both of exemplary embodiment 2 may include about 5% to about 100%, about 10% to about 90%, about 20% to about 80%, about 30% to about 70%, or about 40% to about 50% by weight LLDPE, based on the total weight of the respective layer.
[0104] In one or more embodiments, the second layer, the third layer, or both of exemplary embodiment 2 may have a total weight of about 0% to about 100%, about 0% to about 80%, about 0% to about 60%, about 0% to about 0%, about 0% to about 20%, about 10% to about 100%, about 10% to about 80%, about 10% to about 60%, about 10% to about 40%, or about 10% to about 50% based on the total weight of the respective layer. about 10% by weight to about 20% by weight, about 20% by weight to about 100% by weight, about 20% by weight to about 80% by weight, about 20% by weight to about 60% by weight, about 20% by weight to about 40% by weight, about 40% by weight to about 100% by weight, about 40% by weight to about 80% by weight, about 40% by weight to about 60% by weight, about 60% by weight to about 100% by weight, about 60% by weight to about 80% by weight, or about 80% by weight to about 100% by weight of MDPE.
[0105] In one or more embodiments, the second layer, the third layer, or both of exemplary embodiment 2 may be present in an amount of about 0% to about 100% by weight, about 0% to about 80% by weight, about 0% to about 60% by weight, about 0% to about 0% by weight, about 0% to about 20% by weight, about 10% to about 100% by weight, about 10% to about 80% by weight, about 10% to about 60% by weight, or about 10% to about 40% by weight, based on the total weight of the respective layer. , about 10% by weight to about 20% by weight, about 20% by weight to about 100% by weight, about 20% by weight to about 80% by weight, about 20% by weight to about 60% by weight, about 20% by weight to about 40% by weight, about 40% by weight to about 100% by weight, about 40% by weight to about 80% by weight, about 40% by weight to about 60% by weight, about 60% by weight to about 100% by weight, about 60% by weight to about 80% by weight, or about 80% by weight to about 100% by weight of the polyethylene composition.
[0106] In one or more embodiments, the second layer, the third layer, or both of exemplary embodiment 2 may include less than 50% by weight of low density polyethylene, based on the total weight of the respective layer. In some embodiments, the second layer, the third layer, or both of exemplary embodiment 2 may include about 0% to about 50%, about 0% to about 40%, about 0% to about 20%, about 20% to about 50%, about 20% to about 40%, or about 40% to about 50% by weight of high density polyethylene, based on the total weight of the respective layer.
[0107] Exemplary embodiment 3 As previously mentioned, there is a need for multilayer films that exhibit physical properties such as heat resistance, good gas barrier properties, high stiffness, and excellent toughness without the use of polyamide. In conventional multilayer films, the inclusion of nylon in the film structure exhibits a desirable balance of film properties between dart and film modulus, but can also exhibit process complexity, complex multilayer film structure, non-recyclable multilayer films, and higher material costs compared to those of other polyolefins.
[0108] Reference is now made to an embodiment of a multilayer film described herein, referred to herein as "exemplary embodiment 3." Exemplary embodiment 3 may include a first layer comprising a first polyethylene composition and a first high density polyethylene, a second layer comprising a second polyethylene composition, a second high density polyethylene, and a first low density polyethylene, and a third layer comprising a third polyethylene composition and a second low density polyethylene. Exemplary embodiment 3 multilayer film embodiments comprising the polyethylene compositions disclosed herein may exhibit an excellent balance of film properties (dart and modulus) by exhibiting improved modulus while exhibiting comparable or better dart than multilayer films comprising polyamide.
[0109] The multilayer film of exemplary embodiment 3 can have a variety of thicknesses. In further embodiments, the multilayer film of exemplary embodiment 3 can have a thickness of 25 to 260 μm. In other embodiments, the multilayer film can have an overall thickness of 25 μm to 200 μm, 25 μm to 150 μm, 25 μm to 100 μm, 25 μm to 50 μm, 50 μm to 260 μm, 50 μm to 200 μm, 50 μm to 150 μm, 50 μm to 100 μm, 100 μm to 260 μm, 100 μm to 200 μm, 100 μm to 150 μm, 150 μm to 260 μm, 150 μm to 200 μm, or 200 μm to 260 μm.
[0110] In an embodiment, the multilayer film of exemplary embodiment 3 has a tensile strength of at least 0.925 grams per cubic centimeter (g / cm 3 In another embodiment, the multilayer film of exemplary embodiment 3 may have an overall density of 0.925 g / cm 3 ~0.940g / cm 3 , 0.925g / cm 3 ~0.935g / cm 3 , 0.925g / cm 3 ~0.930g / cm 3 , 0.930g / cm 3 ~0.940g / cm 3 , 0.930g / cm 3 ~0.935g / cm3 , or 0.935 g / cm 3 ~0.940g / cm 3 It could be.
[0111] In an embodiment, the multilayer film of exemplary embodiment 3 may have a dart drop impact of at least 300 grams when measured according to ASTM D1709 Method A. In other embodiments, the multilayer film of exemplary embodiment 3 may have a dart drop impact of 300 grams to 1000 grams, 300 grams to 500 grams, 300 grams to 400 grams, 400 grams to 1000 grams, 400 grams to 1000 grams, or 400 grams to 500 grams when measured according to ASTM D1709 Method A. In further embodiments, the multilayer film of exemplary embodiment 3 may have relatively good dart strength when measured according to ASTM D1709 Method B. In an embodiment, the multilayer film of exemplary embodiment 3 may have a dart drop impact of at least 300 grams when measured according to ASTM D1709 Method B. In other embodiments, the multilayer film of exemplary embodiment 3 may have a dart drop impact of 300 grams to 1000 grams, 300 grams to 500 grams, 300 grams to 400 grams, 400 grams to 1000 grams, 400 grams to 1000 grams, or 400 grams to 500 grams, as measured according to ASTM D1709 Method B.
[0112] The multilayer film of exemplary embodiment 3 may have an average secant modulus in the machine direction of at least 50,000 psi, as measured according to ASTM D882. In other embodiments, the multilayer film may have an average secant modulus in the machine direction of at least 55,000 psi or 60,000 psi, as measured according to ASTM D882. The multilayer film of the present disclosure may have an average secant modulus in the cross direction of at least 55,000 psi, as measured according to ASTM D882. In other embodiments, the multilayer film may have an average secant modulus in the cross direction of at least 60,000 psi or 70,000 psi, as measured according to ASTM D882.
[0113] The core layer of the multilayer film of exemplary embodiment 3 can have a thickness of 0.5 micrometers (μm or microns) to 60 μm. In other embodiments, the second layer can have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0114] The core layer of the multilayer film of exemplary embodiment 3 may comprise 30% to 80% by weight of the total weight of the multilayer film of exemplary embodiment 3. In some embodiments, the core layer may comprise 30% to 60% by weight, 30% to 40% by weight, 40% to 80% by weight, 40% to 60% by weight, or 60% to 80% by weight of the total weight of the multilayer film of exemplary embodiment 3.
[0115] In one or more embodiments, the core layer of exemplary embodiment 3 may comprise 40% to 100% by weight of the polyethylene composition, based on the total weight of the core layer. In some embodiments, the core layer may comprise about 10% to about 100% by weight, about 10% to about 80% by weight, about 10% to about 60% by weight, about 10% to about 40% by weight, about 10% to about 20% by weight, about 20% to about 100% by weight, about 20% to about 80% by weight, about 20% to about 60% by weight, about 20% to about 40% by weight, about 40% to about 100% by weight, about 40% to about 80% by weight, about 40% to about 60% by weight, about 60% to about 100% by weight, about 60% to about 80% by weight, or about 80% to about 100% by weight of the polyethylene composition, based on the total weight of the core layer.
[0116] In embodiments, the core layer of exemplary embodiment 3 may include high density polyethylene (HDPE). In one or more embodiments, the core layer may include up to 50% by weight of high density polyethylene, based on the total weight of the core layer. In some embodiments, the core layer may include about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight of high density polyethylene, based on the total weight of the core layer.
[0117] Optionally, in some embodiments, the core layer of exemplary embodiment 3 may include low density polyethylene (LDPE). In one or more embodiments, the core layer of exemplary embodiment 3 may include less than 50% by weight of low density polyethylene, based on the total weight of the core layer. In some embodiments, the core layer of exemplary embodiment 3 may include about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight of low density polyethylene, based on the total weight of the core layer.
[0118] The second layer, the third layer, or both of the multilayer film of exemplary embodiment 3 may each have a thickness of 0.5 micrometers (μm or microns) to 60 μm. In other embodiments, the second layer, the third layer, or both of the multilayer film of exemplary embodiment 1 may have a thickness of 0.5 μm to 50 μm, 0.5 μm to 25 μm, 0.5 μm to 10 μm, 0.5 μm to 5 μm, 0.5 μm to 1.0 μm, 1.0 μm to 50 μm, 1.0 μm to 25 μm, 1.0 μm to 10 μm, 1.0 μm to 5 μm, 5 μm to 50 μm, 5 μm to 25 μm, 5 μm to 10 μm, 10 μm to 50 μm, 10 μm to 25 μm, or 25 μm to 50 μm.
[0119] The second layer, the third layer, or both of the multilayer film of exemplary embodiment 3 may comprise 20% to 70% by weight of the total weight of the multilayer film of exemplary embodiment 3. In some embodiments, the second layer, the third layer, or both of the multilayer film of exemplary embodiment 1 may comprise 20% to 60% by weight, 20% to 40% by weight, 40% to 70% by weight, 40% to 60% by weight, or 60% to 70% by weight of the total weight of the multilayer film of exemplary embodiment 3.
[0120] In one or more embodiments, the second layer, the third layer, or both of exemplary embodiment 3 may comprise at least 40 wt% of the polyethylene composition of the present disclosure, based on the total weight of the respective layer. In some embodiments, the second layer, the third layer, or both of exemplary embodiment 3 may comprise from about 50 wt% to about 100 wt%, from about 50 wt% to about 80 wt%, from about 50 wt% to about 60 wt%, from about 60 wt% to about 100 wt%, from about 60 wt% to about 80 wt%, or from about 80 wt% to about 100 wt%, based on the total weight of the respective layer, of the polyethylene composition of the present disclosure.
[0121] In one or more embodiments, the second layer, the third layer, or both of exemplary embodiment 3 may include less than 50% by weight of high density polyethylene, based on the total weight of the respective layer. In some embodiments, only one of the second layer or the third layer may include high density polyethylene. In some embodiments, the second layer or the third layer may include about 0% to about 50% by weight, about 0% to about 40% by weight, about 0% to about 20% by weight, about 5% to about 50% by weight, about 5% to about 40% by weight, about 5% to about 20% by weight, about 20% to about 50% by weight, about 20% to about 40% by weight, or about 40% to about 50% by weight of high density polyethylene, based on the total weight of the respective layer.
[0122] In one or more embodiments, the second layer, the third layer, or both of exemplary embodiment 3 may include less than 50% by weight of low density polyethylene, based on the total weight of the respective layer. In some embodiments, the second layer, the third layer, or both may include about 5% to about 50%, about 5% to about 40%, about 5% to about 20%, about 20% to about 50%, about 20% to about 40%, or about 40% to about 50% by weight of low density polyethylene, based on the total weight of the respective layer.
[0123] Methods of producing the films described herein Various methodologies are contemplated for the production of multilayer films. In one or more embodiments, the process for making the multilayer film may include cast film extrusion or blown film extrusion.
[0124] In some embodiments, the process of making a multilayer film may include forming a blown film bubble. In some embodiments, the blown film bubble may be a multilayer blown film bubble. According to this embodiment, further, the multilayer blown film bubble may include at least five layers (according to the first layer, the second layer, the third layer, the fourth layer, and the fifth layer described herein), which may be attached to each other. In some embodiments, each of the first layer and the fifth layer may include a linear low density polyethylene, the second layer and the fourth layer may include a high density polyethylene, and the third layer may include a polyethylene composition as previously described in this disclosure.
[0125] During an embodiment of a blown film process, an extruded film may be formed (inflated) from an extrusion die and pulled up through a tower over a nip. The film may then be wrapped around a core. A folding device may be used to cut and fold the edges of the film before wrapping it around the core, making it difficult to separate the layers of the film, which may be important for shipping applications in general, or for heavy duty shipping sack applications.
[0126] In further embodiments, the blown film bubble may be formed via a blown film extrusion line having a length to diameter ("L / D") ratio of 30 to 1. In some embodiments, the extrusion line may have a blow-up ratio of about 1 to about 5, about 1 to about 3, about 2 to about 5, or about 2 to about 3. In some embodiments, the extrusion line may utilize a die with internal bubble cooling. In some embodiments, the die gap may be about 1 millimeter (mm) to about 5 mm, about 1 mm to about 3 mm, about 2 mm to about 5 mm, or about 2 mm to about 3 mm.
[0127] In some embodiments, the extrusion line may utilize a film thickness gauge scanner. In some embodiments, the multilayer film thickness may be maintained at about 15 μm to 115 μm during the extrusion process. In other embodiments, the multilayer film thickness may be maintained at about 15 μm to 100 μm, 15 μm to 75 μm, 15 μm to 50 μm, 15 μm to 25 μm, 25 μm to 115 μm, 25 μm to 100 μm, 25 μm to 75 μm, 25 μm to 50 μm, 50 μm to 115 μm, 50 μm to 100 μm, 50 μm to 75 μm, 75 μm to 115 μm, 75 μm to 100 μm, or 100 μm to 115 μm.
[0128] In some embodiments, the multilayer blown film bubble forming step can be performed at a temperature of 350-500° F., or 375-475° F. The output rate can be from about 5 lb / hr / in to about 25 lb / hr / in, from about 5 lb / hr / in to about 20 lb / hr / in, from about 5 lb / hr / in to about 15 lb / hr / in, from about 5 lb / hr / in to about 10 lb / hr / in, from about 10 lb / hr / in to about 25 lb / hr / in, from about 10 lb / hr / in to about 20 lb / hr / in, from about 10 lb / hr / in to about 15 lb / hr / in, from about 15 lb / hr / in to about 25 lb / hr / in, from about 15 lb / hr / in to about 20 lb / hr / in, or from about 20 lb / hr / in to about 25 lb / hr / in.
[0129] Goods The present disclosure also relates to articles such as packages formed from the multilayer films of the present disclosure. Such packages can be formed from any of the multilayer films of the present disclosure described herein. The multilayer films of the present disclosure are particularly useful in articles where good tear strength and dart strength are desired.
[0130] Examples of such articles include flexible packages, pouches, stand-up pouches, and pre-made packages or pouches. In some embodiments, the multilayer films or laminates of the present disclosure can be used in heavy duty shipping sacks. In some embodiments, one or more of the aforementioned heavy duty shipping sacks can be utilized in shipping applications.
[0131] Various methods of producing article embodiments from the multilayer films disclosed herein will be familiar to those of skill in the art.
[0132] Polyethylene Composition
[0133] (A) Composition and characterization of polyethylene In one or more embodiments, the polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 For example, an embodiment of the polyethylene composition of the present disclosure may have a density of 0.924 g / cm 3 ~0.931g / cm 3 , 0.924g / cm 3 ~0.928g / cm 3 , 0.927g / cm 3 ~0.931g / cm 3 , or 0.929 g / cm 3 ~0.933g / cm 3 According to additional embodiments, the polyethylene composition may have a density of 0.924 to 0.928, 0.928 g / cm 3 ~0.932g / cm 3 , 0.932g / cm 3 ~0.936g / cm 3 , or any combination of these ranges.
[0134] In one or more embodiments, the polyethylene composition may have a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min, e.g., 0.5 g / 10 min to 1.2 g / 10 min. For example, in one or more embodiments, the polyethylene composition may have a melt index (I2) of 0.25 g / 10 min to 0.5 g / 10 min, 0.5 g / 10 min to 0.7 g / 10 min, 0.7 g / 10 min to 0.9 g / 10 min, 0.59 g / 10 min to 1.1 g / 10 min, 1.1 g / 10 min to 1.3 g / 10 min, 1.3 g / 10 min to 1.5 g / 10 min, 1.5 g / 10 min to 1.7 g / 10 min, 1.7 g / 10 min to 2.0 g / 10 min, or any combination of these ranges. According to additional embodiments, the polyethylene composition may have a melt index (I2) from 0.65 g / 10 min to 1.05 g / 10 min.
[0135] According to embodiments, the polyethylene composition may have a molecular weight distribution, expressed as the ratio of weight average molecular weight to number average molecular weight (Mw / Mn), in the range of 2.5 to 8.0. For example, the polyethylene composition may have a molecular weight distribution of 2.5 to 3.0, 3.0 to 3.5, 3.5 to 4.0, 4.0 to 4.5, 4.5 to 5.0, 5.0 to 5.5, 5.5 to 6.0, 6.0 to 6.5, 6.5 to 7.0, 7.0 to 7.5, 7.5 to 8.0, or any combination of these ranges. In additional embodiments, the polyethylene composition may have a molecular weight distribution of 3.0 to 5.0. As described herein, the molecular weight distribution may be calculated according to gel permeation chromatography (GPC) techniques described herein.
[0136] According to one or more additional embodiments, the polyethylene composition may have a zero shear viscosity ratio of less than 3.0. For example, the polyethylene composition may have a zero shear viscosity ratio of less than 2.9, less than 2.8, less than 2.7, less than 2.6, less than 2.5, less than 2.4, less than 2.3, less than 2.2, less than 2.1, less than 2.0, less than 1.9, less than 1.8, less than 1.7, less than 1.6, less than 1.5, less than 1.4, less than 1.3, less than 1.2, or in some cases less than 1.1. In one or more embodiments, the polyethylene composition may have a zero shear viscosity ratio of at least 1.0.
[0137] As described herein, a polyethylene "fraction" refers to a portion of the overall composition of a polyethylene composition. An embodiment of the present disclosure includes at least a "first polyethylene fraction" and a "second polyethylene fraction." The various fractions included in the polyethylene composition may be quantified via improved comonomer composition distribution (iCCD) analysis by their temperature range in the elution profile. Unless otherwise specified, any elution profile referred to herein is observed via iCCD. Examples of such fractions will be better understood in view of the examples provided herein. In general, the first fraction may include a single peak in the temperature range of the first fraction, and the second fraction may include a single peak in the temperature range of the second fraction. The polyethylene compositions described herein may be referred to as "multimodal," meaning that they include at least two peaks in their elution profile. Some embodiments may be "bimodal," meaning that there are two major peaks.
[0138] With reference to the iCCD distributions already discussed, FIG. 1 shows a schematic of a sample iCCD distribution 100 along with a cumulative weight fraction curve 200. FIG. 1 generally shows several features of the iCCD profile of the polyethylene composition described herein, such as the first fraction, second fraction, and half-peak width, which are discussed in detail herein. Thus, FIG. 1 can be used as a reference with respect to the disclosure related to the iCCD profile provided herein. Specifically, a first fraction 102 and a second fraction 106 are shown. The first fraction 102 has a peak 104, and the second fraction 106 has a peak 108. Each fraction has a half-peak width 110 and 112. It should be understood that the profiles in FIG. 1 are not derived from experiment or observation, but are instead provided for informational purposes to illustrate certain features of the iCCD elution profile.
[0139] In one or more embodiments, the first polyethylene fraction may have a single peak in the temperature range of 45°C to 87°C in the elution profile via iCCD. As used herein, "single peak" refers to an iCCD where a particular fraction contains only a single peak. That is, in some embodiments, the iCCD of the first and second polyethylene fractions contains only an upward sloping region followed by a downward sloping region to form a single peak. In one or more embodiments, the single peak of the first polyethylene fraction may be in the temperature range of 60°C to 85°C, e.g., 70°C to 85°C. Without being bound by theory, it is believed that in at least some embodiments of the polyethylene composition of the present disclosure where a dual reactor design is used for polymerization, there may be a combination of high density crystalline domains and low density amorphous domains. Impact strength is primarily controlled by the concentration of ties connecting the amorphous regions or adjacent lamellae. Density of 0.910 g / cm 3 If the temperature is less than 60° C., the relative tie chain concentration is estimated to be relatively large. The peak of the first polymer fraction in the composition of the present disclosure may be in the temperature range of 60° C. to 85° C., which may provide a higher tie chain concentration to provide functional benefits such as improved toughness.
[0140] It should be understood that the peaks of the first or second polyethylene fractions may not be formed by a local minimum of the respective polyethylene fraction at a definite temperature boundary. That is, the peaks must be in the context of the entire range, rather than a peak formed by a threshold temperature of the polyethylene fraction. For example, if a single peak followed by a single valley exists in a polyethylene fraction (an upward slope followed by a downward slope followed by an upward slope), then only a single peak will exist in such polyethylene fraction.
[0141] In one or more embodiments, the second polyethylene fraction may have a single peak in an iCCD-mediated elution profile in the temperature range of 95° C. to 120° C. The temperature range of the second polyethylene fraction of 95° C. to 120° C. may be desirable because the low molecular weight, high density components at 95° C. to 120° C. allow the polyethylene to achieve a higher overall density while maintaining a lower density fraction when described by the ratio of these two fractions.
[0142] In one or more embodiments, the width of the single peak of the second polyethylene fraction at 50 percent of the peak height may be less than 5.0° C., less than 4° C., or in some cases less than 3° C. Generally, a lower temperature range at 50 percent of the peak height corresponds to a "sharper" peak. Without being bound to a particular theory, it is believed that a "sharper" or "narrower" peak is a property caused by molecular catalysis, indicating minimal comonomer incorporation in the high density fraction, allowing for a greater density split between the two fractions.
[0143] In one or more embodiments, the polyethylene composition may have a minimum in an iCCD-mediated elution profile in the temperature range of 80° C. to 90° C. The minimum may be between the peaks of the first polyethylene fraction and the second polyethylene fraction.
[0144] In embodiments described herein, the first polyethylene fraction area is the area under a single peak of the first polyethylene fraction in the elution profile from 45° C. to 87° C. Similarly, the second polyethylene fraction area is the area under a single peak of the second polyethylene fraction in the elution profile from 95° C. to 120° C. The first polyethylene fraction area and the second polyethylene fraction area may each generally correspond to the total relative mass of each polymer fraction in the polyethylene composition.
[0145] According to one or more embodiments, the difference between the single peak of the second polyethylene fraction and the single peak of the first polyethylene fraction may be at least 10° C. For example, the difference between the single peak of the second polyethylene fraction and the single peak of the first polyethylene fraction may be at least 12° C., 14° C., 16° C., 18° C., or in some cases at least 20° C. In general, the polyethylene fraction area within the iCCD profile may be determined by integrating the iCCD profile between specified start and end temperatures.
[0146] In one or more embodiments, the first polyethylene fraction area may comprise at least 40% of the total area of the elution profile (e.g., at least 42%, at least 44%, at least 46%, at least 48%, at least 50%, at least 52%, or in some cases at least 54% of the total area of the elution profile). For example, the first polyethylene fraction area may comprise between 40% and 65%, e.g., between 42% and 58%, between 43% and 45%, between 45% and 47%, between 53% and 55%, or between 55% and 57% of the total area of the elution profile.
[0147] According to one or more embodiments, the second polyethylene fraction area may comprise at least 25% of the total area of the elution profile (e.g., at least 30%, at least 35%, or in some cases at least 40% of the total area of the elution profile). For example, the first polyethylene fraction area may comprise between 20% and 50%, between 27% and 31%, or between 41% and 48% of the total area of the elution profile.
[0148] According to some embodiments, the first 2 Polyethylene fraction area To versus do No. 1 The ratio of the polyethylene fraction areas may be 0.75 to 2.5 (e.g., 0.75 to 1.0, 1.0 to 1.25, 1.25 to 1.5, 1.5 to 1.75, 1.75 to 2.0, 2.0 to 2.25, 2.25 to 2.5, or any combination of these ranges).
[0149] In one or more embodiments, the polyethylene composition is formed from the polymerization of ethylene and a comonomer, such as a C3-C12 alkene. Contemplated comonomers include C6-C9 alkenes, such as 1-octene and 1-hexene. In one or more embodiments, the comonomer is 1-octene.
[0150] In one or more embodiments, the difference between the single peak of the second polyethylene fraction and the single peak of the first polyethylene fraction is at least 10°C, at least 12.5°C, at least 15°C, at least 17.5°C, or in some cases at least 20°C.
[0151] In one or more embodiments, the first polyethylene fraction may have a melt index (I2) of 0.01 to 0.18 g / 10 min. For example, according to one or more embodiments, the first polyethylene fraction may have a melt index (I2) of 0.01 g / 10 min to 0.03 g / 10 min, 0.03 g / 10 min to 0.05 g / 10 min, 0.05 g / 10 min to 0.07 g / 10 min, 0.07 g / 10 min to 0.09 g / 10 min, 0.09 g / 10 min to 0.11 g / 10 min, 0.11 g / 10 min to 0.13 g / 10 min, 0.13 g / 10 min to 0.15 g / 10 min, 0.15 g / 10 min to 0.18 g / 10 min, or any combination of these ranges.
[0152] In one or more embodiments, the second polyethylene fraction may have a melt index (I2) of 1 to 10,000 g / 10 min. For example, in one or more embodiments, the second polyethylene fraction may have a melt index (I2) of 10 g / 10 min to 1,000 g / 10 min, 20 g / 10 min to 800 g / 10 min, 1 g / 10 min to 100 g / 10 min, 100 g / 10 min to 1,000 g / 10 min, 1,000 g / 10 min to 10,000 g / 10 min, or any combination of these ranges.
[0153] In one or more embodiments, the weight average molecular weight of the second polyethylene fraction can be 120,000 g / mol or less, such as 20,000 g / mol to 120,000 g / mol, or 40,000 g / mol to 65,000 g / mol. In additional embodiments, the weight average molecular weight of the second polyethylene fraction can be 20,000 g / mol to 40,000 g / mol, 40,000 g / mol to 60,000 g / mol, 60,000 g / mol to 80,000 g / mol, 80,000 g / mol to 100,000 g / mol, 100,000 g / mol to 120,000 g / mol, or any combination of these ranges. The molecular weight of the polyethylene fraction can be calculated based on the results of GPC, as described below.
[0154] The polyethylene compositions described herein may have relatively good dart strength when formed into monolayer blown films. According to one or more embodiments, a monolayer blown film formed from the polyethylene composition and having a thickness of 2 mils has a dart drop impact of at least 1000 grams when measured according to ASTM D1709 Method A. In additional embodiments, a monolayer blown film formed from the polyethylene composition and having a thickness of 2 mils has a dart drop impact of at least 1100 grams, at least 1200 grams, at least 1300 grams, at least 1400 grams, at least 1500 grams, at least 1600 grams, at least 1700 grams, at least 1800 grams, at least 1900 grams, or in some cases at least 2000 grams when measured according to ASTM D1709 Method A.
[0155] According to additional embodiments, the polyethylene composition may have a Dow Rheology Index of 5 or less, such as 4 or less, 3 or less, 2 or less, or in some cases 1 or less.
[0156] In one or more embodiments, the polyethylene composition of the present disclosure may further comprise additional components such as one or more additives. Such additives include, but are not limited to, antistatic agents, color enhancers, dyes, lubricants, fillers such as TiO2 or CaCO3, opacifiers, nucleating agents, processing aids, pigments, primary antioxidants, secondary antioxidants, UV stabilizers, antiblocking agents, slip agents, tackifiers, flame retardants, antimicrobial agents, odor reducing agents, antifungal agents, and combinations thereof. The polyethylene composition may contain from about 0.1 to about 10 weight percent of such additives in total, based on the weight of the polyethylene composition including such additives.
[0157] (B) Polymerization Any conventional polymerization process may be used to produce the polyethylene composition described herein. Such conventional polymerization processes include, but are not limited to, slurry polymerization processes, solution polymerization processes using one or more conventional reactors, such as loop reactors, isothermal reactors, stirred tank reactors, simultaneous, continuous batch reactors, and / or any combination thereof. The polyethylene composition may be produced, for example, by a solution phase polymerization process using one or more loop reactors, isothermal reactors, and combinations thereof.
[0158] Generally, the solution phase polymerization process may be carried out in one or more well-stirred reactors, such as one or more isothermal loop reactors or one or more adiabatic reactors, at temperatures ranging from 115 to 250° C. (e.g., 115 to 210° C.) and pressures ranging from 300 to 1,000 psi (e.g., 400 to 800 psi). In some embodiments, in a dual reactor, the temperature of the first reactor is in the range of 115 to 190° C. (e.g., 160 to 180° C.) and the temperature of the second reactor is in the range of 150 to 250° C. (e.g., 180 to 220° C.). In other embodiments, in a single reactor, the temperature of the reactor is in the range of 115 to 250° C. (e.g., 115 to 225° C.).
[0159] The residence time in the solution phase polymerization process can range from 2 to 30 minutes (e.g., 5 to 25 minutes). Ethylene, solvent, hydrogen, one or more catalyst systems, optionally one or more cocatalysts, and optionally one or more comonomers are continuously fed to one or more reactors. Exemplary solvents include, but are not limited to, isoparaffins. For example, such solvents are commercially available under the name ISOPAR E from ExxonMobil Chemical Co., Houston, Texas. The resulting mixture of polyethylene composition and solvent is then removed from the reactor and the polyethylene composition is isolated. The solvent is typically recovered via a solvent recovery unit, such as a heat exchanger and a gas-liquid separator drum, and then recycled to the polymerization system.
[0160] In some embodiments, the polyethylene composition can be produced by solution polymerization in a dual reactor system, e.g., a dual loop reactor system, where ethylene is polymerized in the presence of one or more catalyst systems. In some embodiments, only ethylene is polymerized. Additionally, one or more cocatalysts may be present. In another embodiment, the polyethylene composition can be produced by solution polymerization in a single reactor system, e.g., a single loop reactor system, where ethylene is polymerized in the presence of two catalyst systems. In some embodiments, only ethylene is polymerized.
[0161] (C) Catalyst system Specific embodiments of catalyst systems that can be used in one or more embodiments to produce the polyethylene compositions described herein are now described. It is understood that the catalyst systems of the present disclosure may be embodied in different forms and should not be construed as being limited to the specific embodiments described in this disclosure. Rather, the embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the present subject matter to those skilled in the art.
[0162] The term "independently selected" means 1 , R 2 , R 3 , R 4 , and R 5 The R groups, such as R 1 , R 2 , R 3 , R 4 , and R 5 are all substituted alkyl, or R 1 and R 2 is a substituted alkyl; R 3The terms "aryl" and "aryl" are used herein to indicate that an R group is an alkyl group, and may be aryl, etc. The use of the singular includes the use of the plural and vice versa (e.g., a hexane solvent includes a plurality of hexanes). A named R group will generally have a structure recognized in the art as corresponding to the R group having that name. These definitions are intended to supplement and illustrate, not preclude, definitions known to those of skill in the art.
[0163] The term "procatalyst" refers to a compound that has catalytic activity when combined with an activator. The term "activator" refers to a compound that chemically reacts with a procatalyst to convert the procatalyst into a catalytically active catalyst. As used herein, the terms "cocatalyst" and "activator" are interchangeable terms.
[0164] When used to describe a chemical group that contains a specific carbon atom, "(C x ~C y A bracketed expression having the form "(C1-C)" means that the unsubstituted form of the chemical group has from x carbon atoms to y carbon atoms, inclusive of x and y. For example, (C1-C 40 ) Alkyl is an alkyl group having 1 to 40 carbon atoms in its unsubstituted form. In some embodiments and general structures, specific chemical groups include R S The parenthetical "(C x ~C y ) for the chemical group R S The substituted version can be represented by any group R S Depending on the identity of R, R may contain more than y carbon atoms. For example, S Exactly one group R is phenyl (-C6H5) S (C1~C 40 "(C)alkyl" can contain from 7 to 46 carbon atoms. Thus, the parenthetical "(C)alkyl" is generally used. x ~C y )" is a substituent R SWhen substituted by, the minimum and maximum total number of carbon atoms in the chemical group is the sum of all the substituents R containing carbon atoms in both x and y. S It is determined by adding the combined sum of the carbon atoms derived from
[0165] The term "substituted" refers to the replacement of at least one hydrogen atom (-H) bonded to a carbon or heteroatom of a corresponding unsubstituted compound or functional group with a substituent (e.g., R S The term "persubstituted" means that all hydrogen atoms (H) attached to carbon or heteroatoms of the corresponding unsubstituted compound or functional group are replaced by a substituent (e.g., R S The term "polysubstituted" means that at least two, but fewer than all, of the hydrogen atoms bonded to a carbon or heteroatom of the corresponding unsubstituted compound or functional group are replaced by substituents.
[0166] The term "-H" means a hydrogen or hydrogen radical that is covalently bonded to another atom. "Hydrogen" and "-H" are interchangeable and mean the same thing unless otherwise specified.
[0167] "(C1~C 40 The term "(C1-C)hydrocarbyl" means a hydrocarbon radical of 1 to 40 carbon atoms. 40 The term "hydrocarbylene" means a hydrocarbon diradical of 1 to 40 carbon atoms, each of which may be aromatic or non-aromatic, saturated or unsaturated, straight or branched chain, cyclic (monocyclic and polycyclic, fused and non-fused polycyclic, including bicyclic, containing 3 or more carbon atoms) or acyclic, unsubstituted or substituted with one or more R S has been replaced by
[0168] In the present disclosure, (C1 to C 40 ) Hydrocarbyl is unsubstituted or substituted (C1-C 40 ) Alkyl, (C3-C 40)Cycloalkyl, (C3-C 20 )Cycloalkyl-(C1-C 20 ) Alkylene, (C6-C 40 ) aryl, or (C6-C 20 )Aryl-(C1-C 20 In some embodiments, the above (C1-C 40 Each of the hydrocarbyl groups has up to 20 carbon atoms (i.e., (C1-C 20 ) hydrocarbyl), in other embodiments having up to 12 carbon atoms.
[0169] "(C1~C 40 ) alkyl" and "(C1-C 18 The term "alkyl" refers to an unsubstituted or substituted alkyl group having 1 to 40 carbon atoms or 1 to 18 carbon atoms, respectively, and one or more R S means a saturated linear or branched hydrocarbon radical substituted by 40 Examples of alkyl are unsubstituted (C1-C 20 ) Alkyl, unsubstituted (C1-C 10 ) alkyl, unsubstituted (C1-C5) alkyl, methyl, ethyl, 1-propyl, 2-propyl, 1-butyl, 2-butyl, 2-methylpropyl, 1,1-dimethylethyl, 1-pentyl, 1-hexyl, 1-heptyl, 1-nonyl, and 1-decyl. 40 Examples of substituted (C1-C 20 ) Alkyl, Substituted (C1-C 10 ) alkyl, trifluoromethyl, and [C 45 ] alkyl. 45 The term "alkyl" (with brackets) means that there are up to 45 carbon atoms in the radical, including the substituents, e.g., one R that is (C1-C5) alkyl, S Replaced by (C 27 ~C 40 )alkyl. Each (C1-C5)alkyl can be methyl, trifluoromethyl, ethyl, 1-propyl, 1-methylethyl, or 1,1-dimethylethyl.
[0170] "(C6~C 40 The term "aryl" refers to an unsubstituted or substituted (one or more R S means a monocyclic, bicyclic, or tricyclic aromatic hydrocarbon radical, of which at least 6 to 14 carbon atoms are aromatic ring carbon atoms, the monocyclic, bicyclic, or tricyclic radical containing, respectively, one, two, or three rings, one ring being aromatic, two or three rings being independently fused or non-fused, and at least one of the two or three rings being aromatic. 40 Examples of aryl are unsubstituted (C6-C 20 )Aryl, unsubstituted (C6-C 18 )aryl, 2-(C1-C5)alkyl-phenyl, 2,4-bis(C1-C5)alkyl-phenyl, phenyl, fluorenyl, tetrahydrofluorenyl, indacenyl, hexahydroindacenyl, indenyl, dihydroindenyl, naphthyl, tetrahydronaphthyl, and phenanthrene. 40 Examples of aryl are substituted (C1-C 20 )Aryl, Substituted (C6-C 18 )aryl, 2,4-bis[(C 20 ) alkyl]-phenyl, polyfluorophenyl, pentafluorophenyl, and fluoren-9-on-1-yl.
[0171] "(C3~C 40 The term "cycloalkyl" means unsubstituted or substituted with one or more R S means a saturated cyclic hydrocarbon radical of 3 to 40 carbon atoms, substituted with other cycloalkyl groups, such as (C x ~C y )Cycloalkyl) has x to y carbon atoms and is unsubstituted or has one or more R S Unsubstituted (C3-C 40 Examples of cycloalkyl are unsubstituted (C3-C 20)Cycloalkyl, unsubstituted (C3-C 10 ) cycloalkyl, cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, cycloheptyl, cyclooctyl, cyclononyl, and cyclodecyl. 40 Examples of cycloalkyl are substituted (C3-C 20 )Cycloalkyl, substituted (C3-C 10 ) cycloalkyl, cyclopentanon-2-yl, and 1-fluorocyclohexyl.
[0172] (C1~C 40 Examples of hydrocarbylenes include unsubstituted or substituted (C6-C 40 )Arylene, (C3-C 40 ) cycloalkylene, and (C1-C 40 ) Alkylene (e.g. (C1-C 20 ) alkylene). In some embodiments, the diradicals are on the same carbon atom (e.g., -CH2-), or on adjacent carbon atoms (i.e., 1,2-diradicals), or separated by one, two, or more than two intervening carbon atoms (e.g., 1,3-diradicals, 1,4-diradicals, etc., respectively). Some diradicals include α,ω-diradicals. α,ω-diradicals are diradicals with the greatest carbon backbone spacing between the radical carbons. (C2-C 20 Some examples of alkylene α,ω-diradicals include ethane-1,2-diyl (i.e. -CH2CH2-), propane-1,3-diyl (i.e. -CH2CH2CH2-), 2-methylpropane-1,3-diyl (i.e. -CH2CH(CH3)CH2-). (C6-C 50 ) Some examples of arylene α,ω-diradicals include phenyl-1,4-diyl, naphthalene-2,6-diyl, or naphthalene-3,7-diyl.
[0173] "(C1~C 40 The term "alkylene" may be unsubstituted or may contain one or more R Smeans a saturated straight or branched diradical (i.e., the radical is not on a ring atom) of 1 to 40 carbon atoms, substituted by 50 Examples of alkylene are unsubstituted (C1-C 20 ) alkylene, including unsubstituted -CH2CH2-, -(CH2)3-, -(CH2)4-, -(CH2)5-, -(CH2)6-, -(CH2)7-, -(CH2)8-, -CH2C*HCH3, and -(CH2)4C*(H)CH3, where "C*" represents a carbon atom from which a hydrogen atom has been removed to form a secondary or tertiary alkyl radical. 50 Examples of alkylene are substituted (C1-C 20 ) alkylene, -CF2-, -C(O)-, and -(CH2) 14 C(CH3)2(CH2)5- (i.e., 6,6-dimethyl-substituted normal-1,20-eicosylene). As mentioned above, the two R S Let's do it together (C1~C 18 ) alkylene, so that the substitution (C1-C 50 Examples of alkylene include 1,2-bis(methylene)cyclopentane, 1,2-bis(methylene)cyclohexane, 2,3-bis(methylene)-7,7-dimethyl-bicyclo[2.2.1]heptane, and 2,3-bis(methylene)bicyclo[2.2.2]octane.
[0174] "(C3~C 40 The term "cycloalkylene" refers to a group that is unsubstituted or has one or more R S "R" means a cyclic diradical (i.e., the radicals are on ring atoms) of 3 to 40 carbon atoms substituted by
[0175] The term "heteroatom" refers to an atom other than hydrogen or carbon. Examples of heteroatoms include O, S, S(O), S(O), Si(R C )2, P(R P ), N(R N ), -N=C(R C )2, -Ge(R C )2-, or -Si(RC )-, and each R C , each R N , and each R P is unsubstituted (C1 to C 18 ) hydrocarbyl or -H. The term "heterohydrocarbon" refers to a molecule or molecular backbone in which one or more carbon atoms are replaced with a heteroatom. 40 The term "heterohydrocarbyl" means a heterohydrocarbon radical of 1 to 40 carbon atoms, and is used interchangeably with "(C1-C 40 The term "heterohydrocarbylene" means a heterohydrocarbon diradical of 1 to 40 carbon atoms, each heterohydrocarbon having one or more heteroatoms. The heterohydrocarbyl radical may be present on a carbon atom or a heteroatom, and the heterohydrocarbyl diradical may be present on (1) one or two carbon atoms, (2) one or two heteroatoms, or (3) one carbon atom and one heteroatom. Each (C1 to C 50 ) heterohydrocarbyl and (C1-C 50 ) Heterohydrocarbylene is unsubstituted or substituted (one or more R S The ring structure may be aromatic or non-aromatic, saturated or unsaturated, straight or branched chain, cyclic (including monocyclic and polycyclic, fused polycyclic and non-fused polycyclic) or acyclic.
[0176] (C1~C 40 ) Heterohydrocarbyl is unsubstituted or substituted (C1-C 40 )heteroalkyl, (C1-C 40 ) hydrocarbyl-O-, (C1-C 40 ) Hydrocarbyl-S-, (C1-C 40 ) hydrocarbyl-S(O)-, (C1-C 40 ) hydrocarbyl-S(O)2-, (C1-C 40 ) Hydrocarbyl-Si(R C )2-, (C1~C 40 )hydrocarbyl-N(R N )-, (C1~C 40 ) hydrocarbyl-P(R P )-, (C2~C 40)heterocycloalkyl, (C2-C 19 )Heterocycloalkyl-(C1-C 20 ) alkylene, (C3-C 20 )Cycloalkyl-(C1-C 19 ) Heteroalkylene, (C2-C 19 )Heterocycloalkyl-(C1-C 20 ) Heteroalkylene, (C1-C 40 ) Heteroaryl, (C1-C 19 )Heteroaryl-(C1-C 20 ) Alkylene, (C6-C 20 )Aryl-(C1-C 19 ) heteroalkylene, or (C1-C 19 )Heteroaryl-(C1-C 20 ) heteroalkylene.
[0177] "(C4~C 40 The term "heteroaryl" refers to an unsubstituted or substituted aryl group consisting of a total of 4 to 40 carbon atoms and 1 to 10 heteroatoms (one or more R S means a monocyclic, bicyclic, or tricyclic heteroaromatic hydrocarbon radical, the monocyclic, bicyclic, or tricyclic radical containing, respectively, one, two, or three rings, the two or three rings being independently fused or non-fused, and at least one of the two or three rings being heteroaromatic. Other heteroaryl groups, such as (C4-C 12 ) heteroaryl, etc., (C x ~C y ) Heteroaryl (general) has x to y carbon atoms (e.g., 4 to 12 carbon atoms) and is unsubstituted or has one or more R SThe monocyclic heteroaromatic hydrocarbon radicals are defined in the same manner as those substituted by. The monocyclic heteroaromatic hydrocarbon radicals are 5- or 6-membered rings. The 5-membered ring has 5 minus h carbon atoms, where h is the number of heteroatoms, which can be 1, 2, or 3, and each heteroatom can be O, S, N, or P. Examples of 5-membered heteroaromatic hydrocarbon radicals include pyrrol-1-yl, pyrrol-2-yl, furan-3-yl, thiophen-2-yl, pyrazol-1-yl, isoxazol-2-yl, isothiazol-5-yl, imidazol-2-yl, oxazol-4-yl, thiazol-2-yl, 1,2,4-triazol-1-yl, 1,3,4-oxadiazol-2-yl, 1,3,4-thiadiazol-2-yl, tetrazol-1-yl, tetrazol-2-yl, and tetrazol-5-yl. The six-membered ring has 6 minus h carbon atoms, where h is the number of heteroatoms, which can be 1 or 2, and the heteroatoms can be N or P. Examples of six-membered heteroaromatic hydrocarbon radicals are pyridin-2-yl, pyrimidin-2-yl, and pyrazin-2-yl. The bicyclic heteroaromatic hydrocarbon radicals can be fused 5,6- or 6,6-ring systems. Examples of fused 5,6-ring bicyclic heteroaromatic hydrocarbon radicals include indol-1-yl and benzimidazol-1-yl. Examples of fused 6,6-ring bicyclic heteroaromatic hydrocarbon radicals include quinolin-2-yl and isoquinolin-1-yl. The tricyclic heteroaromatic hydrocarbon radicals can be fused 5,6,5-, 5,6,6-, 6,5,6-, or 6,6,6-ring systems. An example of a fused 5,6,5-ring system is 1,7-dihydropyrrolo[3,2-f]indol-1-yl. An example of a fused 5,6,6-ring system is 1H-benzo[f]indol-1-yl. An example of a fused 6,5,6-ring system is 9H-carbazol-9-yl. An example of a fused 6,5,6-ring system is 9H-carbazol-9-yl. An example of a fused 6,6,6-ring system is acridine-9-yl.
[0178] The heteroalkyl group is any of (C1-C 50) or fewer carbon atoms and one or more heteroatoms. Similarly, heteroalkylene may be a saturated straight or branched chain diradical containing 1 to 50 carbon atoms and one or more heteroatoms. Heteroatoms as defined above include, but are not limited to, Si(R C )3, Ge(R C )3, Si(R C )2, Ge(R C )2, P(R P )2, P(R P ), N(R N )2, N(R N ), N, O, OR C , S, S.R. C , S(O), and S(O), each of the heteroalkyl and heteroalkylene groups may be unsubstituted or may contain one or more R S is replaced by
[0179] Unsubstituted (C2~C 40 Examples of heterocycloalkyl include unsubstituted (C-C 20 )Heterocycloalkyl, unsubstituted (C2-C 10 ) heterocycloalkyl, aziridin-1-yl, oxetan-2-yl, tetrahydrofuran-3-yl, pyrrolidin-1-yl, tetrahydrothiophene-S,S-dioxid-2-yl, morpholin-4-yl, 1,4-dioxan-2-yl, hexahydroazepin-4-yl, 3-oxa-cyclooctyl, 5-thio-cyclononyl, and 2-aza-cyclodecyl.
[0180] The term "halogen atom" or "halogen" refers to a radical of a fluorine atom (F), a chlorine atom (Cl), a bromine atom (Br), or an iodine atom (I). The term "halide" refers to a radical of a fluoride atom (F - ), chloride (Cl - ), bromide (Br - ), or iodide (I - ) refers to the anionic form of a halogen atom.
[0181] The term "saturated" means lacking carbon-carbon double bonds, carbon-carbon triple bonds, and (in heteroatom-containing groups) carbon-nitrogen, carbon-phosphorus, and carbon-silicon double bonds. A saturated chemical group is one or more substituents R S When substituted with, one or more double and / or triple bonds may optionally be replaced by a substituent R S The term "unsaturated" refers to the presence of one or more carbon-carbon double bonds, carbon-carbon triple bonds, and (in heteroatom-containing groups) carbon-nitrogen, carbon-phosphorus, and carbon-silicon double bonds, provided that the substituents R, if present, are not present in the heteroatom-containing group. S The term "aromatic ring" is intended to exclude any double bonds which may be present in the (hetero)aromatic ring or, if present, in the (hetero)aromatic ring.
[0182] According to some embodiments, the catalyst system for producing the polyethylene composition comprises a metal-ligand complex according to formula (I): [ka]
[0183] In formula (I), M is a metal selected from titanium, zirconium, or hafnium, the metal is in a formal oxidation state of +2, +3, or +4, n is 0, 1, or 2, when n is 1, X is a monodentate or bidentate ligand, and when n is 2, each X is a monodentate ligand and is the same or different, the metal-ligand complex as a whole is charge neutral, and each Z is independently selected from -O-, -S-, -N(R N )-, or -P(R P )-, and L is selected from (C1 to C 40 ) hydrocarbylene or (C1-C 40 ) heterohydrocarbylene, (C1-C 40 ) the hydrocarbylene has a moiety that includes a linker skeleton of 1 to 10 carbon atoms (to which L is attached) that connects the two Z groups of formula (I), or (C1 to C 40) heterohydrocarbylene has a moiety containing a linker skeleton of 1 to 10 atoms connecting the two Z groups of formula (I), (C1 to C 40 Each of the 1 to 10 atoms of the 1 to 10 atom linker backbone of the heterohydrocarbylene is independently a carbon atom or a heteroatom, and each heteroatom is independently O, S, S(O), S(O), Si(R C )2, Ge(R C )2, P(R C ), or N(R C ) and each R C However, independently (C1~C 30 ) hydrocarbyl or (C1-C 30 ) heterohydrocarbyl, R 1 and R 8 However, independently, -H, (C1~C 40 ) hydrocarbyl, (C1-C 40 ) heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, -OR C , -SR C , -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R N ) 2NC(O)-, halogen, and a radical having the following formula (II), formula (III), or formula (IV): [ka]
[0184] In formulas (II), (III), and (IV), R 31~35 , R 41~48 , or R 51~59 Each of the following is independently (C1 to C 40 ) hydrocarbyl, (C1-C 40) heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, -N=CHR C , -OR C , -SR C , -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R N )2NC(O)-, halogen, or -H, provided that R 1 or R 8 is a radical having formula (II), formula (III), or formula (IV).
[0185] In formula (I), R 2~4 , R 5~7 , and R 9~16 Each of the following is independently (C1 to C 40 ) hydrocarbyl, (C1-C 40 ) heterohydrocarbyl, -Si(R C )3, -Ge(R C )3, -P(R P )2, -N(R N )2, -N=CHR C , -OR C , -SR C , -NO2, -CN, -CF3, R C S(O)-, R C S(O)2-, (R C )2C=N-, R C C(O)O-, R C OC(O)-, R C C(O)N(R N )-, (R C ) 2NC(O)-, halogen, and -H.
[0186] In some embodiments, the polyethylene composition is formed using a first catalyst according to formula (I) in a first reactor and a different catalyst according to formula (I) in a second reactor.
[0187] In one exemplary embodiment in which a dual loop reactor is used, the procatalyst used in the first loop is zirconium, [[2,2′′-[[bis[1-methylethyl)germylene]bis(methyleneoxy-κO)]bis[3′,5,5″-tris(1,1-dimethylethyl)-5′-octyl[1,1′:3′,1″-terphenyl]-2′-olato-κO]](2-)]dimethyl-, having the chemical formula C 86 H 128 F2GeO4Zr and has the following structure (V): [ka]
[0188] In such an embodiment, the procatalyst used in the second loop is zirconium, [[2,2′′-[1,3-propanediylbis(oxy-κO)]bis[3-[2,7-bis(1,1-dimethylethyl)-9H-carbazol-9-yl]]-5′-(dimethyloctylsilyl)-3′-methyl-5-(1,1,3,3-tetramethylbutyl)[1,1]-biphenyl]-2-olato-κO]](2-)]dimethyl, having the chemical formula C 107 H 154 N2O4Si2Zr and has the following structure (VI): [ka]
[0189] (D) Cocatalyst component The catalyst system comprising the metal-ligand complex of formula (I) can be catalytically activated by any technique known in the art for activating metal-based catalysts for olefin polymerization reactions. For example, the system comprising the metal-ligand complex of formula (I) can be catalytically activated by contacting the complex with an activating cocatalyst or combining the complex with an activating cocatalyst. Activating cocatalysts suitable for use in the present invention include alkylaluminum, polymeric or oligomeric alumoxanes (also known as aluminoxanes), neutral Lewis acids, and non-polymeric, non-coordinating, ion-forming compounds, including the use of such compounds under oxidizing conditions. A suitable activation technique is bulk electrolysis. Combinations of one or more of the foregoing activating cocatalysts and techniques are also contemplated. The term "alkylaluminum" refers to monoalkylaluminum dihydrides or dihalides, dialkylaluminum hydrides or halides, or trialkylaluminum. Examples of polymeric or oligomeric alumoxanes include methylalumoxane, triisobutylaluminum modified methylalumoxane, and isobutylalumoxane.
[0190] The Lewis acid activator (cocatalyst) may be any of the Lewis acid activators described herein, which may be any of the Lewis acid activators having one to three (C1-C 20 In one embodiment, the Group 13 metal compound includes a tri((C1-C) hydrocarbyl substituent. 20 )hydrocarbyl)substituted aluminum or tri((C1-C 20 In another embodiment, the Group 13 metal compound is a tri(hydrocarbyl)-substituted aluminum, tri((C1-C 20 )hydrocarbyl)-boron compounds, tri((C1-C 10 ) alkyl) aluminum, tri((C6-C 18)aryl)boron compounds, and their halogenated (including perhalogenated) derivatives. In further embodiments, the Group 13 metal compound is tris(fluoro-substituted phenyl)borane, tris(pentafluorophenyl)borane. In some embodiments, the activating cocatalyst is tris((C1-C 20 ) hydrocarbyl borates (e.g., trityl tetrafluoroborate) or tri((C 20 )hydrocarbyl)ammonium tetra((C1-C 20 )hydrocarbyl)boranes (e.g., bis(octadecyl)methylammonium tetrakis(pentafluorophenyl)borane). As used herein, the term "ammonium" refers to any of the ((C1-C 20 )Hydrocarbyl)4N + , ((C1~C 20 )hydrocarbyl)3N(H) + , ((C1~C 20 )hydrocarbyl)2N(H)2 + , (C1~C 20 ) HydrocarbylN(H)3 + , or N(H)4 + Each of the nitrogen cations (C1 to C 20 When two or more hydrocarbyls are present, they may be the same or different.
[0191] As a combination of neutral Lewis acid activators (cocatalysts), tri((C1-C4) alkyl)aluminum and tri((C6-C 18)aryl)boron compounds, especially tris(pentafluorophenyl)borane. Other embodiments are such neutral Lewis acid mixtures in combination with polymeric or oligomeric alumoxanes, and a single neutral Lewis acid, especially tris(pentafluorophenyl)borane in combination with polymeric or oligomeric alumoxanes. The molar ratio of (metal-ligand complex):(tris(pentafluorophenylborane):(alumoxane) [e.g., (Group 4 metal-ligand complex):(tris(pentafluorophenylborane):(alumoxane)] is 1:1:1 to 1:10:30, and in other embodiments is 1:1:1.5 to 1:5:10.
[0192] A catalyst system comprising the metal-ligand complex of formula (I) can be activated to form an active catalyst composition by combining one or more cocatalysts, such as cation-forming cocatalysts, strong Lewis acids, or combinations thereof. Suitable activating cocatalysts include polymeric or oligomeric aluminoxanes, particularly methylaluminoxane, as well as inert, compatible, non-coordinating, ion-forming compounds. Exemplary suitable cocatalysts include modified methylaluminoxane (MMAO), bis(hydrogenated tallow alkyl)methyl, tetrakis(pentafluorophenyl)borate (1 - ) amines, and combinations thereof.
[0193] In some embodiments, one or more of the aforementioned activating cocatalysts are used in combination with each other. Particularly preferred combinations are mixtures of tri((C1-C4)hydrocarbyl)aluminum, tri((C1-C4)hydrocarbyl)borane, or ammonium borate with oligomeric or polymeric alumoxane compounds. The ratio of the total number of moles of the one or more metal-ligand complexes of formula (I) to the total number of moles of the one or more activating cocatalysts is 1:10,000 to 100:1. In some embodiments, this ratio is at least 1:5000, in some other embodiments at least 1:1000, and not more than 10:1, and in some other embodiments not more than 1:1. When alumoxane is used alone as the activating cocatalyst, preferably the number of moles of alumoxane used is at least 100 times the number of moles of the metal-ligand complexes of formula (I). When tris(pentafluorophenyl)borane is used alone as the activating cocatalyst, in some other embodiments, the number of moles of tris(pentafluorophenyl)borane used relative to the total number of moles of the one or more metal-ligand complexes of formula (I) is 0.5:1 to 10:1, 1:1 to 6:1, or 1:1 to 5:1. The remaining activating cocatalysts are generally used in a molar amount approximately equal to the total molar amount of the one or more metal-ligand complexes of formula (I).
[0194] Test Method Test methods include:
[0195] Melt Index The melt index I2 (or I2) and I 10(or I10) were measured according to ASTM D-1238 (Method B) at 190°C and loads of 2.16 kg and 10 kg, respectively. The values are reported in g / 10 min. A fraction of a polymer sample is measured by collecting product polymer from the reactor producing that particular fraction or portion of the polymer composition. For example, a first polyethylene fraction can be collected from a reactor producing a lower density, higher molecular weight component of the polymer composition. Prior to the melt index measurement, the polymer solution is dried under vacuum.
[0196] density Samples for density measurements were prepared according to ASTM D4703. Measurements were performed according to ASTM D792, Method B, within 1 hour of sample pressing.
[0197] ASTM D1709 Dirt Drop The Film Dart Drop Test determines the energy at which an impact from a free-falling dart will cause failure of a plastic film under specified conditions. The test result is the energy, expressed as the weight of the projectile dropped from a specified height, that will result in the failure of 50% of the specimens tested.
[0198] After the films were produced, they were conditioned for at least 40 hours at 23°C (+ / -2°C) and 50% RH (+ / -5) according to ASTM standards. Standard test conditions are 23°C (+ / -2°C) and 50% RH (+ / -5) according to ASTM standards.
[0199] Test results may be reported by either Method A, which uses a 1.5 inch diameter dart head and a drop height of 26 inches, or Method B, which uses a 2.0 inch diameter dart head and a drop height of 60 inches. The thickness of the sample is measured at the center of the sample, and then the sample is secured in an annular specimen holder with an inside diameter of 5 inches. The dart is loaded above the center of the sample and released by either a pneumatic or electromagnetic mechanism.
[0200] The test is performed according to the "staircase" method. If a sample fails, the weight of the dart is reduced by a known fixed amount and a new sample is tested. If a sample does not fail, the weight of the dart is increased by a known amount and a new sample is tested. After 20 specimens have been tested, the number of failures is determined. If this number is 10, the test is completed. If this number is less than 10, the test continues until 10 failures are recorded. If this number is greater than 10, the test continues until the total number of non-failures is 10. The dart drop strength was determined from these data, expressed in grams as Type A dart drop impact according to ASTM D1709. All samples analyzed were 2 mils thick.
[0201] Instrumented Dart Impact The instrumented dart impact method is measured on plastic film specimens according to ASTM D7192 using an Instron CEAST 9350 impact tester. The test is performed using a 12.7 mm diameter tap with a hemispherical head, a 75 mm diameter clamp assembly with rubber faced grips. The instrument is equipped with an environmental chamber for testing at low or high temperatures. Typical specimen size is 125 mm x 125 mm. Standard test speed is 200 m / min. Film thickness is 2 mils.
[0202] Creep Zero Shear Viscosity Measurement Method Zero shear viscosity is obtained by creep testing performed on an AR-G2 stress-controlled rheometer (TA Instruments, New Castle, Del.) at 190°C using 25 mm diameter parallel plates. The rheometer oven is set to the test temperature for at least 30 minutes before zeroing the fixture. At the test temperature, a compression molded sample disk is inserted between the plates and allowed to equilibrate for 5 minutes. The upper plate is then lowered 50 μm above the desired test gap (1.5 mm). Any excess material is trimmed away and the upper plate is lowered to the desired gap. Measurements are performed under a nitrogen purge with a flow rate of 5 L / min. The default creep time is set to 2 hours.
[0203] To ensure that the steady state shear rate is low enough to be in the Newtonian region, all of the samples are subjected to a constant low shear stress of 20 Pa. The resulting steady state shear rate was 10 for the samples in this test. -3 ~10 -4 s -1 The steady state is determined by taking a linear regression of all the data in the last 10% time window of a plot of log(J(t)) versus log(t), where J(t) is the creep compliance and t is the creep time. If the slope of the linear regression is greater than 0.97, the steady state is considered to have been reached and the creep test is then stopped. In all cases of this test, the slope meets the criterion within 2 hours. The steady state shear rate is determined from the slope of the linear regression of all the data points in the last 10% time window of a plot of ε versus t, where ε is the strain. The zero shear viscosity is determined from the ratio of the applied stress to the steady state shear rate.
[0204] To determine if the sample has degraded during the creep test, perform small amplitude oscillatory shear tests on the same sample before and after the creep test at 0.1 to 100 rad / s. Compare the complex viscosity values of the two tests. If the difference in viscosity value at 0.1 rad / s is greater than 5%, consider the sample to have degraded during the creep test and discard the results.
[0205] Gel Permeation Chromatography (GPC) The chromatography system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment was set at 160 degrees Celsius and the column compartment was set at 150 degrees Celsius. The columns used were four Agilent "Mixed A" 30 cm 20 micron linear mixed bed columns and a 20 um precolumn. The chromatography solvent used was 1,2,4-trichlorobenzene, which contained 200 ppm of butylated hydroxytoluene (BHT). The solvent source was nitrogen sparged. The injection volume used was 200 microliters and the flow rate was 1.0 milliliters / min.
[0206] Calibration of the GPC column set was performed with 21 narrow molecular weight distribution polystyrene standards with molecular weights ranging from 580 to 8,400,000, arranged in six "cocktail" mixtures with at least 10-fold spacing between individual molecular weights. Standards were purchased from Agilent Technologies. Polystyrene standards were prepared at 0.025 grams in 50 milliliters of solvent for molecular weights 1,000,000 and above, and 0.05 grams in 50 milliliters of solvent for molecular weights below 1,000,000. The polystyrene standards were dissolved at 80 degrees Celsius for 30 minutes with gentle agitation. The peak molecular weights of the polystyrene standards were converted to polyethylene molecular weights using Equation 1 (as described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)). M ポリエチレン =A×(M ポリスチレン ) B (EQ1) where M is the molecular weight, A has a value of 0.4315, and B is equal to 1.0.
[0207] A fifth order polynomial was used to fit each of the polyethylene equivalent calibration points. A small adjustment (approximately 0.375 to 0.445) was made to A to correct for column resolution and band broadening effects for a linear homopolymer polyethylene standard obtained at 120,000 Mw.
[0208] Total plate counts for the GPC column set were performed in decane (prepared at 0.04 g in 50 milliliters of TCB and dissolved for 20 minutes with gentle agitation). Plate counts (Equation 2) and symmetry (Equation 3) were measured with a 200 microliter injection according to the following equations:
number
number
[0209] Samples were prepared in a semi-automated fashion using the PolymerChar "Instrument Control" software to target sample weight of 2mg / ml and add solvent (containing 200ppm BHT) via the PolymerChar high temperature autosampler to a septa-capped vial that had been pre-nitrogen sparged. Samples were dissolved at 160 degrees Celsius with "slow" shaking for 2 hours.
[0210] Mn (GPC) , Mw (GPC) , and Mz(GPC) The calculations were made based on the GPC results using the PolymerChar GPCOne™ software, the baseline-subtracted IR chromatogram at each equally spaced data collection point (i), and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) in Equation 1, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR chromatograph according to Equations 4-6.
number
number
number
[0211] To monitor deviations over time, a flow marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow marker (FM) was used to linearly calibrate the pump flow rate (Flow (apparent)) of each sample by matching the RV of the respective decane peak in the sample (RV (FM sample)) with that of the decane peak in the narrow standard calibration (RV (FM calibrated)). Any change in time of the decane marker peak is thus assumed to be related to a linear shift in flow rate (Flow (effective)) throughout the run. To facilitate the highest accuracy of the RV measurement of the flow marker peak, a least squares fitting routine is used to fit the peaks of the flow marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation is then used to determine the true peak position. After calibrating the system based on the flow marker peaks, the effective flow rate (relative to the narrow standard calibration) is calculated as in Equation 7. Processing of the flow marker peaks was performed by PolymerChar GPCOne™ software. For flow correction to be acceptable, the effective flow should be within + / - 0.5% of the apparent flow. Flow (effective) = Flow (apparent) × (RV(FM calibrated) / RV(FM sample)) (EQ7)
[0212] Improved Comonomer Content Analysis (iCCD) An improved comonomer content analysis method (iCCD) was developed in 2015 (Cong and Parrott et al., WO2017 / 040127A1). iCCD testing was performed using a crystallization elution fractionation instrument (CEF) (PolymerChar, Spain) equipped with an IR-5 detector (PolymerChar, Spain) and a two-angle light scattering detector model 2040 (Precision Detectors, now Agilent Technologies). A guard column of 20-27 micron glass (MoSCi Corporation, USA) packed in stainless steel, 5 cm or 10 cm (length) × 1 / 4 inch (ID), was placed immediately before the IR-5 detector in the detector oven. Orthodichlorobenzene (ODCB, 99% anhydrous grade or technical grade) was used. Silica gel 40 (particle size 0.2-0.5 mm, catalog number 10181-3) was obtained from EMD Chemicals (it can be used to dry the ODCB solvent earlier). The CEF instrument is equipped with an autosampler with N2 purge capability. The ODCB is sparged with dry nitrogen (N2) for 1 h prior to use. Sample preparation was performed using the autosampler at 4 mg / mL (unless otherwise specified) with shaking at 160 °C for 1 h. Injection volume was 300 μl. The temperature profile for the iCCD was crystallization from 105 °C to 30 °C at 3 °C / min, thermal equilibration at 30 °C for 2 min (including setting the soluble fraction elution time to 2 min), elution from 30 °C to 140 °C at 3 °C / min. The flow rate during crystallization is 0.0 ml / min. The flow rate during elution is 0.50 ml / min. Data was collected at one data point / sec.
[0213] The iCCD column was packed with gold-coated nickel particles (Bright 7GNM8-NiS, Nippon Chemical Industrial Co.) in a 15 cm (length) x ¼ inch (ID) stainless steel tube. Column packing and conditioning were performed using the slurry method according to reference (Cong, R, Parrott, A., Hollis, C., Cheatham, M. WO2017 / 040127A1). The final pressure, including packing of the TCB slurry, was 150 bar.
[0214] The column temperature was calibrated using a linear homopolymer polyethylene reference material in ODCB with zero comonomer content, melt index (I2) of 1.0, and polydispersity M w / M n was performed using a mixture of 1.0 mg / ml (approximately 2.6) and eicosane (2 mg / ml) for conventional gel permeation chromatography. iCCD temperature calibration consisted of four steps: (1) calculating the delay volume, defined as the temperature offset between the measured peak elution temperatures of eicosane minus 30.00°C, and (2) subtracting the temperature offset of the elution temperature from the iCCD raw temperature data. It is noted that this temperature offset is a function of experimental conditions such as elution temperature, elution flow rate, etc.; (3) a linear calibration line is constructed converting elution temperatures over the range of 30.00°C to 140.00°C, such that the linear homopolymer polyethylene reference has a peak temperature at 101.0°C and eicosane has a peak temperature of 30.0°C; (4) for soluble fractions measured isothermally at 30°C, elution temperatures below 30.0°C are linearly extrapolated by using an elution heating rate of 3°C / min according to the reference (Cerk and Cong et al., US 9,688,795).
[0215] Comonomer content versus iCCD elution temperature was constructed using 12 reference materials (ethylene homopolymers and single-site metallocene catalyzed ethylene-octene random copolymers with weight average molecular weights ranging from 35,000 to 128,000 ethylene equivalents). All of these reference materials were analyzed at 4 mg / mL in the same manner as previously specified. The reported elution peak temperatures were linearly fitted to the linear equation y=-6.3515x.+101.00, where y represents the iCCD elution temperature, x represents octene mole %, and R 2 was 0.978.
[0216] The molecular weights of the polymers and the molecular weights of the polymer fractions were determined directly from the LS detector (at a 90 degree angle) and the concentration detector (IR-5) according to the Rayleigh-Gans-Debys approximation (Striegel and Yau, Modern Size Exclusion Liquid Chromatograms, pp. 242 and 263) by assuming a form factor of 1 and all virial coefficients of zero. An integration window is set to integrate all chromatograms at elution temperatures ranging from 23.0 to 120 °C (temperature calibration specified above).
[0217] Calculation of molecular weight (Mw) from iCCD involves four steps: (1) Measure the inter-detector offset. The offset is defined as the geometric volume offset between the LS detector and the concentration detector. It is calculated as the difference in elution volume (mL) of the polymer peak between the concentration detector and the LS chromatogram. This is converted to a temperature offset by using the elution heat rate and elution flow rate. A linear high-density polyethylene (comonomer content zero, melt index (I2) 1.0, polydispersity M w / M nConventional gel permeation chromatography (GPC) is used at about 2.6). The same experimental conditions as the normal iCCD method described above are used, except for the following parameters: crystallization from 140°C to 137°C at 10°C / min, soluble fraction elution time at 137°C for 1 minute thermal equilibration, soluble fraction (SF) time of 7 minutes, and elution from 137°C to 142°C at 3°C / min. The flow rate during crystallization is 0.0 mL / min. The flow rate during elution is 0.80 mL / min. The sample concentration is 1.0 mg / mL. (2) Shift each LS data point in the LS chromatogram to correct for inter-detector offset before integration. (3) The baseline-subtracted LS and concentration chromatograms are integrated over the elution temperature range of step (1). The MW detector constant is calculated using HDPE samples of known MW in the range of 100,000-140,000 MW and the area ratios of the LS and concentration integrated signals. (4) The Mw of the polymer was calculated using the ratio between the integrated light scattering detector (at a 90 degree angle) and the concentration detector and using the MW detector constant.
[0218] The half-width calculation is defined as the temperature difference between the front and rear temperatures at half the maximum peak height, where the front temperature at half the maximum peak is searched forward from 35.0°C and the rear temperature at half the maximum peak is searched backward from 119.0°C.
[0219] Zero Shear Viscosity Ratio (ZSVR) ZSVR is defined as the ratio of the zero shear viscosity (ZSV) of a branched polyethylene material to the ZSV of a linear polyethylene material at equivalent weight average molecular weight (Mw-gpc) according to Equations (EQ) 10 and 11 below:
number
number
[0220] ZSV values are obtained from creep tests at 190°C according to the method described above. Mw-gpc values are determined by conventional GPC method (Equation 5 in the description of conventional GPC method). The correlation between ZSV of linear polyethylene and its Mw-gpc was established based on a series of linear polyethylene reference materials. A description of the ZSV-Mw relationship can be found in ANTEC Abstract: Karjala, Teresa P., Sammler, Robert L., Mangnus, Marc A., Hazlitt, Lonnie G., Johnson, Mark S., Hagen, Charles M. Jr., Huang, Joe WL, Reichek, Kenneth N., “Detection of low levels of long-chain branching in polyolefins”, Annual Technical Conference-Society of Plastics Engineers (2008), 66th 887-891.
[0221] MD tearing MD tear was measured according to ASTM D-1922. The force in grams required to propagate a tear across a film specimen is measured using an Elmendorf tear tester. Acting by gravity, the pendulum oscillates in an arc, tearing the specimen from a pre-cut slit. The tear is propagated in the cross direction. Samples are conditioned at temperature for a minimum of 40 hours prior to testing.
[0222] Dynamic Rheological Analysis To characterize the rheological behavior of substantially linear ethylene polymers, S Lai and GW Knight (ANTEC '93 Proceedings, Insite™ Technology Polyolefins (ITP)—New Rules in the Structure / Rheology Relationship of Ethylene &-Olefin Copolymers, New Orleans, La., May 1993) introduced a new rheological measurement that represents the "normalized relaxation time as a result of long chain branching" of a polymer, the Dow Rheological Index (DRI). S. Lai et al. (ANTEC '94, Dow Rheology Index (DRI) for Insite™ Technology Polyolefins (ITP): Unique structure-Processing Relationships, pp. 1814-1815) defined the DRI as the extent to which the rheology of ethylene-octene copolymers, known as ITPs (Dow's Insite Technology Polyolefins), which incorporate long chain branching in the polymer backbone, deviates from the rheology of conventional linear homogeneous polyolefins reported to have no long chain branching (LCB) by the following normalized equation: DRI=[3650000X(τ0 / η0)-1] / 10 where τ0 is the characteristic relaxation time for the material and τ0 is the zero shear rate complex viscosity for the material. The DRI is calculated by a least-squares fit of the rheological curve (dynamic complex viscosity η*(ω) versus applied frequency (ω), e.g., 0.01-100 rad / sec), as described in U.S. Pat. No. 6,114,486, with the following generalized intersection equation: η*(ω)=η0 / [1+(ω τ0) n ] where n is the power law exponent of the material, and η*(ω) and ω are the measured complex viscosity and applied frequency data, respectively.
[0223] Dynamic rheology measurements are performed in a dynamic rheometer (e.g., ARES rheometer from TA Instruments) with 25 mm diameter parallel plates in dynamic mode under an inert atmosphere according to ASTM D4440. In all experiments, the rheometer is thermally stabilized at 190°C for at least 30 minutes before inserting the properly stabilized (by antioxidant) and compression molded sample into the parallel plates. The plates are then closed with a positive normal force recorded on the meter to ensure good contact. After about 5 minutes at 190°C, the plates are lightly compressed and excess polymer around the plates is trimmed. The plate is left for another 10 minutes until the thermal stability and normal force return to zero. In other words, all measurements are performed after the sample has equilibrated at 190°C for about 15 minutes and are performed under a full nitrogen blanket.
[0224] Two strain sweep (SS) experiments are first performed at 190 °C to determine the linear viscoelastic strain that produces a torque signal greater than 10% of the transducer's lower scale over the full frequency (e.g., 0.01-100 rad / s) range. The first SS experiment is performed at a low applied frequency of 0.1 rad / s. This test is used to determine the sensitivity of the torque at low frequencies. The second SS experiment is performed at a high applied frequency of 100 rad / s. This is to ensure that the selected applied strain is well within the linear viscoelastic region of the polymer so that the oscillatory rheological measurements do not induce structural changes in the polymer during testing. Additionally, a time sweep (TS) experiment is performed at the selected strain (determined by the SS experiment) but at a low applied frequency of 0.1 rad / s to confirm the stability of the sample during testing.
[0225] Values of the storage (or elastic) modulus, loss (or viscous) modulus (G"), complex modulus (G*), complex viscosity (η*) and tan δ (ratio of loss modulus to storage modulus G'VG') were obtained as a function of frequency (ω) at a given temperature (e.g. 190°C).
[0226] ASTM D882 MD and CD, 1% and 2% Secant Modulus The MD (machine direction) and CD (cross direction) secant modulus of the films were determined according to ASTM D882. The reported secant modulus value was the average of five measurements.
[0227] Puncture strength The puncture test determines the resistance of a film to penetration of a probe at a standard slow, single test speed. The puncture test method is based on ASTM D5748. After film production, the film was conditioned for at least 40 hours at 23°C (+ / - 2°C) and 50% RH (+ / - 5) as per ASTM standard. Standard test conditions are 23°C (+ / - 2°C) and 50% RH (+ / - 5) as per ASTM standard. Puncture was measured with a tensile tester. Square specimens were cut from the sheet to a size of "6" x 6". The specimen was clamped into a "4" diameter" circular specimen holder and the puncture probe was forced into the center of the clamped film at a crosshead speed of 10 inches per minute. The internal test method is based on ASTM D5748 with one modification. This method differed from the ASTM D5748 method in that the probe used was a "0.5 inch diameter" polished steel ball on a "0.25 inch" support (rather than the 0.75 inch diameter pear-shaped probe specified in D5748).
[0228] There was a maximum travel length of "7.7 inches" to prevent damage to the test fixture. There was no gauge length and the probe was as close as possible to, but not touching, the specimen before testing. A single thickness measurement was taken at the center of the specimen. For each specimen, the maximum force, force at break, penetration distance, and energy to break were determined. A total of five specimens were tested to determine the average puncture value. The puncture probe was cleaned using a "Kimwipe" after each specimen. EXAMPLES
[0229] The following examples are illustrative of features of the present disclosure and are not intended to limit the scope of the disclosure. The following experiments analyzed the performance of embodiments of the multilayer films described herein.
[0230] Example 1A: Preparation of Polyethylene Compositions 1 to 5 Polyethylene compositions 1-5 described according to one or more of the detailed descriptions were prepared by the methods and utilizing the catalysts and reactors described below.
[0231] All raw materials (monomers and comonomers) as well as process solvents (high purity narrow boiling range isoparaffinic solvent, Isopar-E) are purified with molecular sieves prior to introduction into the reaction environment. Hydrogen is supplied under pressure as a high purity grade and is not further purified. The reactor monomer feed stream is pressurized to above the reaction pressure via a mechanical compressor. The solvent and comonomer feeds are pressurized to above the reaction pressure via pumps. The individual catalyst components are manually batch diluted with purified solvent and pressurized to above the reaction pressure. All reaction feed streams are metered using mass flow meters and independently controlled by computer automated valve control systems.
[0232] As shown in Figure 3, two reactor systems are used in a series configuration. Each continuous solution polymerization reactor consists of a liquid-filled, non-adiabatic, isothermal circulating loop reactor replicating a continuous stirred tank reactor (CSTR) with heat removal. Independent control of all fresh solvent, monomer, comonomer, hydrogen, and catalyst component feeds is possible. The total fresh feed streams to each reactor (solvent, monomer, comonomer, and hydrogen) are temperature controlled to maintain a single solution phase by passing the feed streams through heat exchangers. The total fresh feed to each polymerization reactor is injected into the reactor at two locations with approximately equal reactor volume between each injection location. The fresh feed is controlled with each injector receiving half of the total fresh feed mass flow rate. The catalyst components are injected into the polymerization reactors through injection needles. The main catalyst component feed is computer controlled to maintain the monomer conversion of each reactor at a specific target. The cocatalyst components are fed based on a specific calculated molar ratio to the main catalyst component. Immediately after the injection point of each reactor feed, the feed stream is mixed with the contents of a circulation polymerization reactor with static mixing elements. The contents of each reactor are continuously circulated through a heat exchanger that serves to remove most of the heat of reaction, with the coolant side temperature serving to maintain an isothermal reaction environment at a specific temperature. Circulation around each reactor loop is provided by a pump.
[0233] In a dual reactor in series configuration, the effluent from the first polymerization reactor (containing solvent, monomer, comonomer, hydrogen, catalyst components, and polymer) exits the first reactor loop and is added to the second reactor loop.
[0234] The second reactor effluent enters a zone where it is deactivated by addition and reaction with a suitable reagent (water). At this same reactor exit site, other additives are added for polymer stabilization (typical antioxidants suitable for stabilization during extrusion and film production, such as octadecyl 3,5-di-Tert-butyl-4-hydroxyhydrocinnamate, tetrakis(methylene(3,5-di-Tert-butyl-4-hydroxyhydrocinnamate))methane, and tris(2,4-di-Tert-butyl-phenyl)phosphite).
[0235] Following catalyst deactivation and additive addition, the reactor effluent enters a devolatilization system where polymer is removed from the non-polymer stream. The isolated polymer melt is pelletized and collected. The non-polymer stream passes through various equipment that separates most of the ethylene removed from the system. Most of the solvent and unreacted comonomer are recycled to the reactor after passing through a purification system. Small amounts of solvent and comonomer are purged from the process.
[0236] The reactor stream feed data flows used to generate the examples and corresponding to the values in Table 1 are illustrated diagrammatically in Figure 3. The data are presented so that the complexity of the solvent recycle system is taken into account and the reaction system can be more easily treated as a once-through flow diagram. Table 1B shows the catalysts referenced in Table 1A. [Table 1-1] [Table 1-2] [Table 2]
[0237] Example 1B: Preparation of Polyethylene Composition 6 Polyethylene compositions 6 and 7 described according to one or more of the detailed description were prepared by the methods and utilizing the catalysts and reactors described below.
[0238] All raw materials (monomers and comonomers) as well as process solvents (high purity narrow boiling range isoparaffinic solvent, Isopar-E) are purified with molecular sieves prior to introduction into the reaction environment. Hydrogen is supplied under pressure as a high purity grade and is not further purified. The reactor monomer feed stream is pressurized to above the reaction pressure via a mechanical compressor. The solvent and comonomer feeds are pressurized to above the reaction pressure via pumps. The individual catalyst components are manually batch diluted with purified solvent and pressurized to above the reaction pressure. All reaction feed streams are metered using mass flow meters and independently controlled by computer automated valve control systems.
[0239] Two reactor systems are used in a parallel configuration. Each continuous solution polymerization reactor consists of a liquid-filled, non-adiabatic, isothermal circulating loop reactor replicating a continuous stirred tank reactor (CSTR) with heat removal. Independent control of all fresh solvent, monomer, comonomer, hydrogen, and catalyst component feeds is possible. The total fresh feed streams to each reactor (solvent, monomer, comonomer, and hydrogen) are temperature controlled to maintain a single solution phase by passing the feed streams through heat exchangers. The total fresh feed to each polymerization reactor is injected into the reactor at two locations, with approximately equal reactor volumes between each injection location. The fresh feed is controlled with each injector receiving half of the total fresh feed mass flow rate. The catalyst components are injected into the polymerization reactors through specially designed injection needles. The main catalyst component feed is computer controlled to maintain the monomer conversion of each reactor at a specific target. The cocatalyst components are fed based on a specific calculated molar ratio to the main catalyst component. Immediately after the point of injection of each reactor feed, the feed streams are mixed with the contents of the circulation polymerization reactor using static mixing elements. The contents of each reactor are continuously circulated through heat exchangers that serve to remove most of the heat of reaction, with the coolant side temperature serving to maintain an isothermal reaction environment at a specific temperature. Circulation around each reactor loop is provided by pumps.
[0240] The effluent streams from the first and second polymerization reactors are combined before any additional processing. This final combined reactor effluent enters a zone where the effluent is deactivated by addition and reaction with a suitable reagent (water). At this same reactor exit site, other additives are added for polymer stabilization (typical antioxidants suitable for stabilization during extrusion and blown film production, such as octadecyl 3,5-di-Tert-butyl-4-hydroxyhydrocinnamate, tetrakis(methylene(3,5-di-Tert-butyl-4-hydroxyhydrocinnamate))methane, and tris(2,4-di-Tert-butyl-phenyl)phosphite).
[0241] Following catalyst deactivation and additive addition, the reactor effluent enters a devolatilization system where polymer is removed from the non-polymer stream. The isolated polymer melt is pelletized and collected. The non-polymer stream passes through various equipment that separates most of the ethylene removed from the system. Most of the solvent and unreacted comonomer are recycled to the reactor after passing through a purification system. Small amounts of solvent and comonomer are purged from the process.
[0242] The reactor stream feed data flows used to generate the examples and corresponding to the values in Table 2A are illustrated diagrammatically in Figure 4. The data are presented so that the complexity of the solvent recycle system is taken into account and the reaction system can be more easily treated as a once-through flow diagram. Table IB shows the catalysts referenced in Table 2A of Example 1A. [Table 3]
[0243] Example 2: Comparative Compositions A to J Comparative compositions A-C were prepared by the methods described herein below. Comparative compositions D-F are bimodal polyethylene compositions generally prepared using the catalyst system and process provided for preparing the inventive first composition in PCT Publication No. 2015 / 200743. Comparative compositions G-J are commercially available polyethylene compositions. Table 3 shows the commercially available polyethylene compositions of comparative compositions G-J. [Table 4]
[0244] The preparation of comparative compositions A-C is described as follows: All raw materials (monomers and comonomers) as well as process solvents (high purity narrow boiling range isoparaffinic solvent, Isopar-E) are purified with molecular sieves prior to introduction into the reaction environment. Hydrogen is supplied under pressure as a high purity grade and is not further purified. The reactor monomer feed stream is pressurized to above the reaction pressure via a mechanical compressor. The solvent and comonomer feeds are pressurized to above the reaction pressure via pumps. The individual catalyst components are manually batch diluted with purified solvent and pressurized to above the reaction pressure. All reaction feed streams are metered using mass flow meters and independently controlled by computer automated valve control systems.
[0245] Two reactor systems are used in a series configuration. Each continuous solution polymerization reactor consists of a liquid-filled, non-adiabatic, isothermal circulating loop reactor replicating a continuous stirred tank reactor (CSTR) with heat removal. Independent control of all fresh solvent, monomer, comonomer, hydrogen, and catalyst component feeds is possible. The total fresh feed streams to each reactor (solvent, monomer, comonomer, and hydrogen) are temperature controlled to maintain a single solution phase by passing the feed streams through heat exchangers. The total fresh feed to each polymerization reactor is injected into the reactor at two locations, with approximately equal reactor volume between each injection location. The fresh feed is controlled with each injector receiving half of the total fresh feed mass flow rate. The catalyst components are injected into the polymerization reactors through injection needles. The main catalyst component feed is computer controlled to maintain the monomer conversion of each reactor at a specific target. The cocatalyst components are fed based on a specific calculated molar ratio to the main catalyst component. Immediately after the injection point of each reactor feed, the feed stream is mixed with the contents of a circulation polymerization reactor with static mixing elements. The contents of each reactor are continuously circulated through a heat exchanger that serves to remove most of the heat of reaction, with the coolant side temperature serving to maintain an isothermal reaction environment at a specific temperature. Circulation around each reactor loop is provided by a pump.
[0246] In a dual reactor in series configuration, the effluent from the first polymerization reactor (containing solvent, monomer, comonomer, hydrogen, catalyst components, and polymer) exits the first reactor loop and is added to the second reactor loop.
[0247] The second reactor effluent enters a zone where it is deactivated by addition and reaction with a suitable reagent (water). At this same reactor exit site, other additives are added for polymer stabilization (typical antioxidants suitable for stabilization during extrusion and film production, such as octadecyl 3,5-di-Tert-butyl-4-hydroxyhydrocinnamate, tetrakis(methylene(3,5-di-Tert-butyl-4-hydroxyhydrocinnamate))methane, and tris(2,4-di-Tert-butyl-phenyl)phosphite).
[0248] Following catalyst deactivation and additive addition, the reactor effluent enters a devolatilization system where polymer is removed from the non-polymer stream. The isolated polymer melt is pelletized and collected. The non-polymer stream passes through various equipment that separates most of the ethylene removed from the system. Most of the solvent and unreacted comonomer are recycled to the reactor after passing through a purification system. Small amounts of solvent and comonomer are purged from the process.
[0249] The reactor stream feed data flows used to generate the examples and corresponding to the values in Table 4A are illustrated diagrammatically in Figure 3. The data are presented so that the complexity of the solvent recycle system is taken into account and the reaction system can be more easily treated as a once-through flow diagram. Table IB shows the catalysts and cocatalysts shown in Table 4A. [Table 5]
[0250] Example 3: Analysis of Polyethylene Samples Polyethylene compositions 1-6 of Examples 1A and 1B, comparative polyethylene compositions A-C of Example 2, and commercially available comparative polyethylene samples D-J of Example 2 were analyzed by iCCD. iCCD data for polyethylene composition 5 is shown in Figure 2. Additional data generated from iCCD testing of all samples is shown in Tables 5A and 5B. Specifically, Tables 5A and 5B include an analysis of the iCCD data including the areas (45-87°C and 95-120°C) of the first and second polyethylene fractions, respectively. Additional data for each example composition is also provided, including overall density, dart strength (Method A), melt index, and weight average molecular weight of the second PE fraction. These properties are based on monolayer blown films made entirely from each polyethylene sample.
[0251] To perform the dart test and other tests based on the formed film, polyethylene samples were used to form 2 mil blown films. Specifically, monolayer blown films are produced through an Egan Davis Standard extruder with a 3.5 inch ID half grooved barrel, a 30 / 1 L / D ratio, a barrier screw, and an Alpine air ring. The extrusion line has an 8 inch die with internal bubble cooling. The extrusion line also has a film thickness gauge scanner. The film production conditions were: film thickness was maintained at 2 mils (0.001in or 0.0254mm), blow up ratio (BUR) was 2.5, die gap was 70 mils, and frost line height (FLH) was 37 inches. The output rate was constant at 260 lbs / hr. [Table 6] [Table 7]
[0252] The results show that all of the comparative compositions have a viscosity of at least 0.924 g / cm 3 It can be seen that the comparative samples do not exhibit comparable dart strengths at overall densities of 0.924 g / cm. For example, some comparative samples have high dart strengths, but these samples have much lower densities. 3 ~0.936g / cm 3 ) indicates a much lower dart strength (e.g., less than 1000 grams).
[0253] Additionally, several compositions of Example 1 had a Dow Rheology Index of less than 10, such as 3.5, 4.6, and 5.5.
[0254] Example 4: Evaluation of the Use of the Disclosed Polyethylene Composition in a Core Layer Example 4 compares four multilayer film samples (Film 4-1, Film 4-2, Film 4-3, and Film 4-4) prepared according to the embodiments disclosed and described herein with comparative multilayer film samples (Comparative 4-A, Comparative 4-B, Comparative 4-C, Comparative 4-D, Comparative 4-E, Comparative 4-F, Comparative 4-G, and Comparative 4-H). For all samples produced and tested in Example 4, the multilayer film had three layers, including two outer layers and one core layer. The material used for the outer layer was the same for each outer layer and remained constant throughout each sample. To observe the effect of utilizing various materials in the core layer, the samples tested in Example 4 each included a core layer composed of one material, but this material was different for the various samples. In Example 4, samples were produced with both an overall thickness of 55 μm and an overall thickness of 45 μm to observe the downgauge effect.
[0255] Films 4-1, 4-2, 4-3, and 4-4 are examples of multilayer films according to some embodiments of the present disclosure. As shown in Table 6 below, polyethylene composition 1 (PE Comparative Example 1) prepared according to Example 1A was utilized in Films 4-1 and 4-3, polyethylene composition 2 (PE Comparative Example 2) prepared according to Example 1A was utilized in Films 4-2 and 4-4, and Films 4-1, 4-2, 4-3, and 4-4 each contained DOWLEX™ GM 8051 polyethylene (melt index: 2.16 kg and 0.9 g / 10 min at 190° C., density: 0.921 g / cm 3 ). 3 , commercially available from The Dow Chemical Company).
[0256] Also, as shown in Table 6 below, Comparative 4-A, Comparative 4-B, Comparative 4-C, Comparative 4-D, Comparative 4-E, Comparative 4-F, Comparative 4-G, and Comparative 4-H each contain two or more DOWLEX™ GM 8051 polyethylene (melt index: 0.9 g / 10 min at 2.16 kg and 190° C., density: 0.921 g / cm 3, commercially available from The Dow Chemical Company), DOWLEX™ 2049 polyethylene (melt index: 1.0 g / 10 min at 2.16 kg and 190° C., density: 0.926 g / cm 3 , commercially available from The Dow Chemical Company), 6D20 polypropylene resin (melt index: 1.9 g / 10 min at 2.16 kg and 230° C., density: 0.900 g / cm 3 , commercially available from Braskem "rPP"), and two bimodal polyethylene compositions (melt index: 0.85 g / 10 min at 2.16 kg and 190° C., density: 0.918 g / cm 3 , "Bimodal PE1") and (Melt index: 0.85 g / 10 min at 2.16 kg and 190°C, density: 0.926 g / cm 3 and "Bimodal PE2"). Bimodal PE1 and Bimodal PE2 are generally polyethylene compositions prepared using the catalyst systems and processes provided for preparing the invention 1 compositions in PCT Publication No. 2015 / 200743.
[0257] To produce the sample films of Example 4, the materials in Table 6 were formed into blown films on a 5-layer extrusion line with a blow-up ratio (BUR) of 2.5, a die temperature of 230°C, a die gap of 1.8 mm, a melt temperature of 225°C, and a speed of 12.5 kg / hr.
[0258] The structure and layer distribution of the multilayer film of Example 4 are provided in Table 6 as follows: [Table 8]
[0259] Specific properties of the multilayer film of Example 4 were measured in accordance with the test methods disclosed herein, and these properties are provided in Table 7. [Table 9]
[0260] As shown in Table 7, for films with a total thickness of 55 μm, Comparative 4-A exhibited the lowest secant modulus of all samples tested. Comparative 4-D exhibited a secant modulus of 448 MPa, but a Dart B of less than 300 g. Comparative 4-B, Comparative 4-C, and Film 4-1 exhibited relatively equivalent secant modulus properties. However, Film 4-1 exhibited a higher Dart B than Comparative 4-B and Comparative 4-C. Film 4-2 exhibited the highest Dart B and secant modulus values of all samples tested in Example 4 with a total thickness of 55 μm.
[0261] As shown in Table 7, for films with a total thickness of 45 μm, Comparative 4-E exhibited the second lowest secant modulus of all samples tested. Comparative 4-H exhibited a secant modulus of 493 MPa, but a Dart B of less than 300 g. Comparative 4-F, Comparative 4-G, and Film 4-3 exhibited relatively equivalent secant modulus properties. However, Film 4-3 exhibited a higher Dart B than Comparative 4-F and Comparative 4-G. Film 4-4 exhibited the highest Dart B of all samples tested in Example 4 with a total thickness of 45 microns, and the highest secant modulus of all samples with a polyethylene core and a total thickness of 45 microns.
[0262] Thus, the results in Table 7 show that embodiments of the present disclosure including a core layer incorporating the polyethylene compositions described herein can provide unexpectedly superior dart impact resistance compared to multilayer films including core layers comprising other polyolefins, where a balance between stiffness (2% secant modulus) and dart impact resistance can be observed in the multilayer films that was not achieved by the comparative multilayer films. This balance between stiffness and toughness can be advantageous in various packaging applications, especially when less gauge is used (down gauge).
[0263] Example 5: Evaluation of the Use of the Disclosed Polyethylene Compositions in Core and Outer Layers Example 5 compares three multilayer film samples prepared according to some embodiments described herein (Film 5-1, Film 5-2, and Film 5-3) with comparative multilayer film samples (Comparative 5-A, Comparative 5-B, Comparative 5-C, Comparative 5-D). For all samples produced and tested in Example 5, the multilayer film had three layers, including two outer layers and one core layer. In the outer layers of all samples tested in Example 5, the LDPE material used and the weight percentage of the LDPE material in the outer layer remained constant. In the core layers of all samples tested in Example 5, the masterbatch material, the amount of masterbatch material, and the HDPE material used in the core layer remained constant. In Example 5, samples were produced having an overall thickness of 4.0 mils (101.6 μm) and an overall thickness of 4.23 mils (107.4 μm) to observe the effect of downgauging on certain properties. The balance of materials in the outer and core layers was varied for the samples of Example 5 to observe the effect of utilizing the disclosed polyethylene composition in the core and outer layers.
[0264] Films 5-1, 5-2, and 5-3 are examples of multilayer films according to some embodiments described herein. As shown in Table 8 below, polyethylene composition 4 (PE Comparative Example 4) prepared according to Example 1A was utilized in Film 5-1, polyethylene composition 2 prepared according to Example 1A was utilized in Films 5-2 and 5-3, and AGILITY™ 1200 polyethylene (Melt Index: 0.25 g / 10 min at 2.16 kg and 190° C., Density: 0.919 g / cm 3 ) was utilized in Film 5-2 and Film 5-3. 3 , commercially available from The Dow Chemical Company) was utilized in Film 5-1, Film 5-2, and Film 5-3, and DMDH 6400 polyethylene (melt index: 0.80 g / 10 min at 2.16 kg and 190° C., density: 0.961 g / cm 3, commercially available from The Dow Chemical Company) was utilized in Films 5-1, 5-2, and 5-3, and masterbatch TiO2 (commercially available from Ampacet Corporation) was utilized in Films 5-1, 5-2, and 5-3.
[0265] As shown in Table 8 below, Comparative Examples 5A to 5D are made of EXCEED™ 1018 polyethylene (melt index: 1.0 g / 10 min at 2.16 kg and 190° C., density: 0.918 g / cm 3 , commercially available from ExxonMobil), AGILITY™ 1200 polyethylene (melt index: 0.25 g / 10 min at 2.16 kg and 190° C., density: 0.919 g / cm 3 , commercially available from The Dow Chemical Company), DMDH 6400 polyethylene (melt index: 0.80 g / 10 min at 2.16 kg and 190° C., density: 0.961 g / cm 3 , commercially available from The Dow Chemical Company), bimodal PE1, bimodal PE2, and masterbatch TiO2 (commercially available from Ampacet Corporation).
[0266] To produce the sample film of Example 5, the materials in Table 8 were formed into a film on an Alpine 7-layer blown film line. The extruder size was 2.5 inches, the die diameter was 7.87 inches, the die gap was 78.7 mils, the blow-up ratio (BUR) was 1.75, the melt temperature was 458°F to 472°F, the output rate was 250 lbs / hr, the line speed was 56 ft. / min (3 layer coextrusion), and the frost line height (FLH) was 36 inches.
[0267] The structure and layer distribution of the multilayer film of Example 5 are provided in Table 8 as follows: [Table 10]
[0268] The properties of the multilayer film of Example 5 were measured according to the test methods disclosed herein and are provided in Table 9. [Table 11]
[0269] As shown in Table 9, Film 5-3 exhibited the highest dart, followed by Films 5-1 and 5-2. Additionally, Film 5-1 exhibited the lowest tensile creep properties, followed by Films 5-2, Comparative 5-A, and Film 5-3. Thus, the results in Table 9 indicate that such embodiments described herein that include a core layer incorporating the polyethylene compositions described herein can provide unexpectedly superior dart impact resistance and tensile creep properties compared to multilayer films that include core layers that include other polyolefins.
[0270] Example 6: Evaluation of the use of the disclosed polyethylene compositions in a core layer to reduce or eliminate the need for polyamide Example 6 compares two multilayer film samples prepared according to some embodiments described herein (Film 6-1 and Film 6-2) with comparative multilayer film samples (Comparative 6-A, Comparative 6-B, Comparative 6-C, and Comparative 6-D). For all samples produced and tested in Example 6, the multilayer film had three layers, including two outer layers and one core layer. In the outer layers of all samples tested in Example 6, the LDPE material used, the weight percentage of the LDPE material in the outer layer, the HDPE material used, and the weight percentage of the HDPE material in the outer layer remained constant. To observe the effect of utilizing the disclosed polyethylene composition in the core layer and the outer layer, the ratio of polyethylene to HDPE in the core layer was varied in an attempt to maintain a similar film density across each sample.
[0271] To produce the film of Example 6, the amounts of materials listed in Tables 10 and 11 were blown into film on a 7-layer Alpine coextrusion blowline. Blown film line parameters included a 9.84 mil die, a 78.7 mil die gap, a 2.5:1 BUR, a speed of 350 lbs / hr, a die temperature of approximately 450°F, a melt temperature of 439°F to 497°F (depending on the material being extruded), and an actual speed of 11.3 lbs / hr / in.
[0272] Reference structures containing polyamide (nylon) were produced as shown in Table 10. Materials used to produce Comparative 6-A included bimodal PE1, ELITE™ 5960 polyethylene (Melt index: 0.85 g / 10 min at 2.16 kg and 190° C., Density: 0.962 g / cm 3 , commercially available from The Dow Chemical Company), and DOW LDPE 132I (Melt Index: 0.25 g / 10 min at 2.16 kg and 190° C., Density: 0.921 g / cm 3 , commercially available from The Dow Chemical Company), Bynel 41E710 anhydride modified LLDPE resin (melt index: 1.2 g / 10 min at 2.16 kg and 190° C., density: 0.862 g / cm 3 , commercially available from The Dow Chemical Company), and Ultramid C40L polyamide (commercially available from BASF).
[0273] The structure and layer distribution of Comparative 6-A is shown in Table 10. [Table 12]
[0274] Film 6-1 and Film 6-2 are examples of multilayer films according to some embodiments described herein. Polyethylene composition 2 (Comparative PE 2) prepared according to Example 1A was utilized in Film 6-1, and polyethylene composition 3 (Comparative PE 3) prepared according to Example 1A was utilized in Film 6-2, as shown in Table 11 below. Films 6-1 and 6-2 contained bimodal PE1, ELITE™ 5960 polyethylene (Melt index: 0.85 g / 10 min at 2.16 kg and 190° C., Density: 0.962 g / cm 3 , commercially available from The Dow Chemical Company), DOW LDPE 132I (Melt index: 0.25 g / 10 min at 2.16 kg and 190° C., density: 0.921 g / cm 3 , commercially available from The Dow Chemical Company), and two polyethylene compositions (melt index: 0.85 g / 10 min at 2.16 kg and 190° C., density: 0.925 g / cm 3 Also included are "Bimodal PE3" ("Bimodal PE4"). Bimodal PE3 is generally a polyethylene composition prepared using the catalyst system and process provided for preparing the first composition in PCT Publication No. 2015 / 200743.
[0275] As shown in Table 11 below, Comparative 6-B, Comparative 6-C, and Comparative 6-D have bimodal PE1 (melt index: 0.85 g / 10 min at 2.16 kg and 190 ° C., density: 0.918 g / cm 3 , commercially available from The Dow Chemical Company), ELITE™ 5960 polyethylene (melt index: 0.85 g / 10 min at 2.16 kg and 190° C., density: 0.962 g / cm 3 , commercially available from The Dow Chemical Company), DOW LDPE 132I (Melt index: 0.25 g / 10 min at 2.16 kg and 190° C., density: 0.921 g / cm 3, commercially available from The Dow Chemical Company), as well as comparative composition C of Example 2 ("Comparative Example C of Example 2") were utilized.
[0276] The structure of the film produced in Example 6 is shown below. [Table 13]
[0277] The properties of the multilayer film of Example 6 were measured according to the test methods disclosed herein, and these properties are provided in Table 12. [Table 14]
[0278] As shown in Table 12, Film 6-1 exhibited the highest dart, followed by Comparative 6-A and Film 6-2. Additionally, Film 6-2 exhibited the highest modulus, followed by Film 6-1, and Comparative 6-A exhibited the lowest modulus. Thus, the results in Table 12 demonstrate that such embodiments described herein that incorporate the polyethylene compositions described herein and include a core layer that does not incorporate a polyamide core layer can provide an unexpected balance of superior dart impact resistance and tensile creep properties as compared to multilayer films that include core layers that include other polyolefins or polyamides.
[0279] It will be apparent that modifications and variations are possible without departing from the scope of the present disclosure, as defined in the appended claims. More specifically, although certain aspects of the present disclosure have been identified herein as preferred or particularly advantageous, it is contemplated that the present disclosure is not necessarily limited to those aspects. It should be noted that the present invention includes the following aspects. [Aspect 1] A multilayer film, A first layer, 1. A polyethylene composition comprising: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile measured by an improved comonomer composition distribution (iCCD) analysis method, wherein a first polyethylene fraction area is an area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in an elution profile measured by the iCCD analysis method, wherein a second polyethylene fraction area is an area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C, The polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min, wherein the first polyethylene fraction area constitutes at least 40% of the total area of the elution profile, 2 Polyethylene fraction area To versus do The above 1 a ratio of the areas of the polyethylene fractions of the first and second polyethylene fractions is 0.75 to 2.5, and the width of the single peak of the second polyethylene fraction at 50 percent of the peak height is less than 5.0° C.; a second layer comprising a first polyolefin; a third layer comprising a second polyolefin; Including, the first layer is disposed between the second layer and the third layer; A multi-layer film, wherein the first polyolefin and the second polyolefin are the same or different. [Aspect 2] The first polyolefin composition, the second polyolefin composition, or both, have a viscosity of 0.870 g / cm 3 ~0.970g / cm 3 2. The multilayer film of embodiment 1, comprising polyethylene having a density of: [Aspect 3] the first layer is in direct contact with the second layer and the third layer; 3. The multilayer film of claim 1 or 2, wherein the second layer and the third layer are outermost layers of the multilayer film. [Aspect 4] 0.924g / cm 3 ~0.936g / cm 3 and a ratio of weight average molecular weight to number average molecular weight (M w / M n 4. The multilayer film of any one of embodiments 1 to 3, having a molecular weight distribution, expressed as a function of molecular weight (Mw / Mn), in the range of 2.5 to 8.0. [Aspect 5] 5. The multilayer film of any one of claims 1 to 4, wherein the multilayer film has a thickness of less than 500 micrometers (μm). [Aspect 6] The first layer has a hardness of 0.940 g / cm as measured in accordance with ASTM 742. 3 6. The multilayer film of any one of the preceding claims, further comprising a polyethylene having a density greater than [Aspect 7] A multilayer film, a first layer, which constitutes 10% by weight to 80% by weight of the total weight of the multilayer film, the first layer comprising: 1. A polyethylene composition comprising: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile measured by an improved comonomer composition distribution (iCCD) analysis method, wherein a first polyethylene fraction area is an area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in an elution profile measured by the iCCD analysis method, wherein a second polyethylene fraction area is an area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C, The polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min, wherein the first polyethylene fraction area constitutes at least 40% of the total area of the elution profile, 2 Polyethylene fraction area To versus do The above 1 a ratio of the areas of the polyethylene fractions of the first and second polyethylene fractions is 0.75 to 2.5, and the width of the single peak of the second polyethylene fraction at 50 percent of the peak height is less than 5.0° C.; 0.910g / cm 3 ~0.936g / cm 3 a second layer comprising a first linear low density polyethylene having a density of 0.910g / cm 3 ~0.936g / cm 3 a third layer comprising a second linear low density polyethylene having a density of Including, the first layer is disposed between the second layer and the third layer; A multilayer film, wherein the first linear low density polyethylene and the second linear low density polyethylene are the same or different. [Aspect 8] 8. The multilayer film of embodiment 7, wherein the multilayer film has a dart drop impact of at least 400 grams as measured according to ASTM D1709 method B. [Aspect 9] 9. The multilayer film of embodiment 7 or 8, wherein the multilayer film has an average secant modulus in the machine direction of from 29,000 psi to 37,000 psi, the average secant modulus being measured according to ASTM D882. [Aspect 10] A multilayer film, A first layer, 0.940 g / cm when measured according to ASTM 742 3 ~0.970g / cm 3 a high density polyethylene composition having a density of 1. A polyethylene composition comprising: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile measured by an improved comonomer composition distribution (iCCD) analysis method, wherein a first polyethylene fraction area is an area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in an elution profile measured by the iCCD analysis method, wherein a second polyethylene fraction area is an area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C, The polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min, wherein the first polyethylene fraction area constitutes at least 40% of the total area of the elution profile, 2 Polyethylene fraction area To versus do The above 1 a polyethylene composition having a ratio of a polyethylene fraction area of from 0.75 to 2.5 and a width of the single peak of the second polyethylene fraction at 50 percent of the peak height of less than 5.0° C.; A second layer comprising at least 50 wt. % of a first linear low density polyethylene based on the total weight of the second layer, the first linear low density polyethylene having a viscosity of 0.910 g / cm 3 ~0.936g / cm 3 a second layer having a density of A third layer comprising at least 50 wt. % of a second linear low density polyethylene based on the total weight of the third layer, the second linear low density polyethylene having a viscosity of 0.910 g / cm 3 ~0.936g / cm 3 and a third layer having a density of Including, the first layer is disposed between the second layer and the third layer; A multilayer film, wherein the first linear low density polyethylene and the second linear low density polyethylene are the same or different. [Aspect 11] 11. The multilayer film of embodiment 10, wherein the multilayer film has a cross-direction tensile creep of less than 50% at 1.4 kg / 50° C. / 5 hr, as measured according to ASTM 2990. [Aspect 12] 12. The multilayer film of claim 10 or 11, wherein the multilayer film has a dart drop impact of at least 600 grams as measured according to ASTM D1709 method B. [Aspect 13] A multilayer film, A first layer, 0.940g / cm 3 ~0.970g / cm 3 a first polyethylene having a density of 0.924g / cm 3 ~0.936g / cm 3 a first layer comprising a first polyethylene composition having a density of A second layer, 0.940g / cm 3 ~0.970g / cm 3 a second polyethylene having a density of 0.916g / cm 3 ~0.935g / cm3 a first low density polyethylene having a density of 0.924g / cm 3 ~0.936g / cm 3 a second layer comprising a second polyethylene composition having a density of A third layer, 0.916g / cm 3 ~0.935g / cm 3 a second low density polyethylene having a density of 0.924g / cm 3 ~0.936g / cm 3 a third layer comprising a third polyethylene composition having a density of Including, the first layer is disposed between the second layer and the third layer; the first polyethylene and the second polyethylene are the same or different; the first low density polyethylene and the second low density polyethylene are the same or different; The first polyethylene composition, the second polyethylene composition, and the third polyethylene composition are the same or different compositions, each comprising: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile measured by an improved comonomer composition distribution (iCCD) analysis method, wherein a first polyethylene fraction area is an area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in an elution profile measured by the iCCD analysis method, wherein a second polyethylene fraction area is an area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C, The polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3and a melt index (I2) of 0.25 g / 10 min to 2.0 g / 10 min, wherein the first polyethylene fraction area constitutes at least 40% of the total area of the elution profile, 2 Polyethylene fraction area To versus do The above 1 a ratio of the areas of the polyethylene fractions of said first polyethylene fraction and said second polyethylene fraction is 0.75 to 2.5, and the width of the single peak of said second polyethylene fraction at 50 percent of the peak height is less than 5.0°C. [Aspect 14] 14. The multilayer film of embodiment 13, wherein the multilayer film has a dart drop impact of at least 350 grams as measured according to ASTM D1709 method B. [Aspect 15] 15. The multilayer film of claim 13 or 14, wherein the multilayer film has an average secant modulus in the machine direction greater than 50,000 psi, the average secant modulus measured according to ASTM D882.
Claims
1. A multilayer film, A first layer, 1. A polyethylene composition comprising: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile by improved comonomer composition distribution (iCCD) analysis, wherein a first polyethylene fraction area is the area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in an elution profile measured by the iCCD analysis method, wherein a second polyethylene fraction area is an area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C; The polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I 2 a first layer comprising a polyethylene composition having a first polyethylene fraction area constituting at least 40% of the total area of the elution profile, a ratio of the first polyethylene fraction area to the second polyethylene fraction area being 0.75 to 2.25, and a width of the single peak of the second polyethylene fraction at 50 percent of the peak height being less than 5.0° C.; a second layer comprising the first polyolefin; a third layer comprising a second polyolefin; and Including, the first layer is disposed between the second layer and the third layer; A multi-layer film, wherein the first polyolefin and the second polyolefin are the same or different.
2. The first polyolefin composition, the second polyolefin composition, or both, have a viscosity of 0.870 g / cm 3 ~0.970g / cm 3 10. The multilayer film of claim 1, comprising a polyethylene having a density of
3. the first layer is in direct contact with the second layer and the third layer; The multilayer film of claim 1 or 2, wherein the second layer and the third layer are outermost layers of the multilayer film.
4. 0.924 g / cm 3 ~0.936g / cm 3 and a ratio of weight average molecular weight to number average molecular weight (M w / M n The multilayer film according to any one of claims 1 to 3, having a molecular weight distribution, expressed as a function of molecular weight (Mw / Mn), in the range of 2.5 to 8.
0.
5. The multilayer film of any one of claims 1 to 4, wherein the multilayer film has a thickness of less than 500 micrometers (μm).
6. The first layer has a toughness of 0.940 g / cm as measured in accordance with ASTM 742. 3 The multilayer film of any one of claims 1 to 5, further comprising a polyethylene having a density greater than
7. A multilayer film, a first layer, comprising 10% to 80% by weight of the total weight of the multilayer film, the first layer comprising:
1. A polyethylene composition comprising: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile by improved comonomer composition distribution (iCCD) analysis, wherein a first polyethylene fraction area is the area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in an elution profile measured by the iCCD analysis method, wherein a second polyethylene fraction area is an area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C; The polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I 2 a first layer comprising a polyethylene composition having a first polyethylene fraction area constituting at least 40% of the total area of the elution profile, a ratio of the first polyethylene fraction area to the second polyethylene fraction area being 0.75 to 2.25, and a width of the single peak of the second polyethylene fraction at 50 percent of the peak height being less than 5.0° C.; 0.910 g / cm 3 ~0.936g / cm 3 a second layer comprising a first linear low density polyethylene having a density of 0.910 g / cm 3 ~0.936g / cm 3 a third layer comprising a second linear low density polyethylene having a density of Including, the first layer is disposed between the second layer and the third layer; A multilayer film, wherein the first linear low density polyethylene and the second linear low density polyethylene are the same or different.
8. 8. The multilayer film of claim 7, wherein the multilayer film has a dart drop impact of at least 400 grams as measured according to ASTM D1709 Method B.
9. 9. The multilayer film of claim 7 or 8, wherein the multilayer film has an average secant modulus in the machine direction of from 29,000 psi to 37,000 psi, the average secant modulus being measured according to ASTM D882.
10. A multilayer film, A first layer, 0.940 g / cm when measured according to ASTM 742 3 ~0.970g / cm 3 a high density polyethylene composition having a density of 1. A polyethylene composition comprising: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile by improved comonomer composition distribution (iCCD) analysis, wherein a first polyethylene fraction area is the area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in an elution profile measured by the iCCD analysis method, wherein a second polyethylene fraction area is an area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C; The polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I 2 a polyethylene composition having a first polyethylene fraction area constituting at least 40% of the total area of the elution profile, a ratio of the first polyethylene fraction area to the second polyethylene fraction area being 0.75 to 2.25, and a width of the single peak of the second polyethylene fraction at 50 percent of the peak height being less than 5.0° C.; A second layer comprising at least 50 wt. % of a first linear low density polyethylene based on the total weight of the second layer, the first linear low density polyethylene having a viscosity of 0.910 g / cm 3 ~0.936g / cm 3 a second layer having a density of A third layer comprising at least 50 wt. % of a second linear low density polyethylene based on the total weight of the third layer, the second linear low density polyethylene having a viscosity of 0.910 g / cm 3 ~0.936g / cm 3 a third layer having a density of Including, the first layer is disposed between the second layer and the third layer; A multilayer film, wherein the first linear low density polyethylene and the second linear low density polyethylene are the same or different.
11. 11. The multilayer film of claim 10, wherein the multilayer film has a cross-direction tensile creep of less than 50% at 1.4 kg / 50° C. / 5 hrs as measured according to ASTM 2990.
12. 12. The multilayer film of claim 10 or 11, wherein the multilayer film has a dart drop impact of at least 600 grams as measured according to ASTM D1709 Method B.
13. A multilayer film, A first layer, 0.940 g / cm 3 ~0.970g / cm 3 a first polyethylene having a density of 0.924 g / cm 3 ~0.936g / cm 3 a first layer comprising a first polyethylene composition having a density of A second layer, 0.940 g / cm 3 ~0.970g / cm 3 a second polyethylene having a density of 0.916 g / cm 3 ~0.935g / cm 3 a first low density polyethylene having a density of 0.924 g / cm 3 ~0.936g / cm 3 a second layer comprising a second polyethylene composition having a density of A third layer, 0.916 g / cm 3 ~0.935g / cm 3 a second low density polyethylene having a density of 0.924 g / cm 3 ~0.936g / cm 3 a third layer comprising a third polyethylene composition having a density of Including, the first layer is disposed between the second layer and the third layer; the first polyethylene and the second polyethylene are the same or different; the first low density polyethylene and the second low density polyethylene are the same or different; The first polyethylene composition, the second polyethylene composition, and the third polyethylene composition are the same or different compositions, each comprising: (a) a first polyethylene fraction having a single peak in a temperature range of 45°C to 87°C in an elution profile by improved comonomer composition distribution (iCCD) analysis, wherein a first polyethylene fraction area is the area in the elution profile under the single peak of the first polyethylene fraction at 45°C to 87°C; (b) a second polyethylene fraction having a single peak in the temperature range of 95°C to 120°C in an elution profile measured by the iCCD analysis method, wherein a second polyethylene fraction area is an area in the elution profile under the single peak of the second polyethylene fraction at 95°C to 120°C; The polyethylene composition has a viscosity of 0.924 g / cm 3 ~0.936g / cm 3 and a melt index (I 2 ), wherein the first polyethylene fraction area constitutes at least 40% of the total area of the elution profile, the ratio of the first polyethylene fraction area to the second polyethylene fraction area is from 0.75 to 2.25, and the width of the single peak of the second polyethylene fraction at 50 percent of the peak height is less than 5.0° C.
14. 14. The multilayer film of claim 13, wherein the multilayer film has a dart drop impact of at least 350 grams as measured according to ASTM D1709 Method B.
15. 15. The multilayer film of claim 13 or 14, wherein the multilayer film has an average secant modulus in the machine direction greater than 50,000 psi, the average secant modulus being measured according to ASTM D882.
Citation Information
Patent Citations
Multilayered film for packaging material and production thereof
JP2000343658A
Impact Modification of Thermoplastics with Ethylene / α-Olefin Copolymers
JP2008545018A
Polyolefin composition
JP2016505694A
A polyolefin composition
US20160194464A1
Multimodal ethylene-based polymer compositions having improved toughness
WO2019133373A1